Natural deep eutectic solvents (NADES): dual functionality in the extraction and stabilization of polyphenols, terpenoids and nitrogen compounds - Gerardo Valles-Salas; Juliana Morales-Castro; Claudia I. Gamboa-Gómez; Blanca E. Morales-Contreras; Walfred Rosas-Flores; L. Araceli Ochoa-Martínez; Juan C. Contreras-Esquivel; Ana M. Ávila-Galván; Orlando A. Manzanares-Meza (Food Chemistry, 2026)

Urban land use and management drive soil pollution across urban and nearby natural ecosystems in the Iberian Peninsula - Andrea C. Sala-Navarro; Nuria Casado-Coy; Axel Campos-Castro; Camelia Algora; Elena Aguilar-Santana; Kaiyan Zhai; Josu G. Alday; Cristina Armas; C. Guillermo Bueno; Leonor Calvo; María Dolores Carmona-Yáñez; Giada Centenaro; et al. (Journal of Hazardous Materials, 2026)

Methoxyacetic acid exposure in rats induces N-butyrylglycinuria consistent with beta-oxidation impairment - Samuele Sala; Janonna Kadyrov; Andres Bernal; Andres M. Castillo; Preechaya Naraprasertkul; Nadia Paesalasakul; Proud Bekanan; Issariya Dhitsuwon; Thanaporn Kulthawatsiri; Reika Masuda; Manthan Sharma; Jutarop Phetcharaburanin; et al. (Archives of Toxicology, 2026)

Sensory maps in the telencephalic pallium of goldfish - F. M. Ocaña; A. Gómez; C. Salas; F. Rodríguez (Brain Structure and Function, 2026)
The functional organization of the teleost telencephalic pallium remains poorly understood, particularly regarding the presence of modality-specific sensory domains and their topographic arrangement. Here, we used in vivo wide-field voltage-sensitive dye imaging to map sensory-evoked neural activity across the dorsal surface of the telencephalic pallium of adult goldfish. Somatosensory, auditory, gustatory, and visual stimulation revealed distinct, modality-specific domains located within the dorsomedial (Dm) and dorsolateral (Dl) pallium, that closely matched cytoarchitectural boundaries. Within Dm, somatosensory and auditory stimuli activated partially overlapping territories in the caudal subregion (Dm4), exhibiting clear somatotopic and tonotopic organization along the mediolateral axis. Gustatory stimulation selectively engaged Dm3, where different tastants activated spatially distinct but partially overlapping domains. A more rostral subregion (Dm2) responded only to high-intensity somatosensory stimulation, suggesting involvement in processing negatively valenced inputs, whereas the adjacent Dm1 remained unresponsive to all sensory modalities tested. Visual stimulation activated a circumscribed area within the dorsolateral pallium (Dld2). Pharmacological blockade of ionotropic glutamate receptors markedly reduced sensory-evoked responses, indicating that these maps depend on glutamatergic synaptic transmission. Together, these findings reveal a more elaborate and functionally differentiated pallial organization than previously recognized and provide the first direct evidence for modality-specific topographic sensory maps in the teleost pallium. More broadly, they offer a new framework for understanding how sensory, affective, and mnemonic functions are organized within the teleost pallium and for comparing this organization with distributed pallial systems in other vertebrates.

Corrigendum to “Biotechnological valorisation of Spent Automotive Catalytic Converters: Marine microorganisms in PGE leaching and recovery” [J. Environ. Chem. Eng. 13(5) (2025) 118729] - L. Vitale; P. Tedesco; C. Galasso; G.A. Vitale; G. Varola; G. Della Sala; F. Palma Esposito; S. Balzano; J. Ghani; D. de Pascale; E. Dinelli; T.C. Meisel; et al. (Journal of Environmental Chemical Engineering, 2026)

Effect of graphene quantum dot size on the capacitance of rGO-based supercapacitors fabricated with a sustainable electrolyte (seawater) - R.A. Mendoza-Jiménez; J. Oliva; T.A. Esquivel-Castro; C. Rodriguez-Gonzalez; P. Salas (Chemical Engineering Journal, 2026)

Measuring trauma: a preliminary analysis of the hurricane-related traumatic experiences questionnaire - Sumeyra Sahbaz; Duyen Vo; Christopher P. Salas-Wright; Mildred M. Maldonado-Molina; Aaron Clark-Ginsberg; Eric C. Brown; José Rodríguez; Sehun Oh; Melissa M. Bates; Seth J. Schwartz (Climate and Development, 2026)

Left and right-side echocardiographic measurement of pulmonary artery stiffness in thoroughbred racehorses - C. Bozzola; L. Stucchi; G. Sala; L. Schinardi; G. Stancari; E. Zucca (Journal of Equine Veterinary Science, 2026)

Interlaboratory clinical chemistry parameter variation in seven-day acute hydrazine toxicity studies in the Sprague-Dawley rat - Janonna Kadyrov; Samuele Sala; Lucy Grigoroff; Reika Masuda; Samantha Lodge; Timothy M. Ebbels; Michael D. Reily; Donald Robertson; Lois Lehman-McKeeman; John Shockcor; Bruce D. Car; Craig Thomas; et al. (Archives of Toxicology, 2026)
Clinical chemistry retains its position as a cornerstone of toxicological assessment, yet inter-laboratory variability in baseline values remains a challenge for the integration and interpretation of multisite datasets. This study leveraged a publicly available clinical chemistry database to assess the impact of inter-laboratory variability in response to hydrazine-induced steatosis. Seventeen clinical chemistry and physico-chemical parameters were evaluated in response to a single dose of hydrazine (at 30 mg/kg or 90 mg/kg) administered to Sprague-Dawley rats ( n = 83) across five different pharmaceutical companies and compared with sham-dosed control animals. Hydrazine exposure produced a distinct and consistent biochemical signature at 48 h post-dose across the combined sample set from all laboratory sites, characterised by increased serum bilirubin and BUN and decreased serum protein concentrations, alongside atypical reductions in ALT and AST due to transaminase inhibition. Despite sizable inter-laboratory differences in response when considering single assays, multivariate analysis of the complete dataset was able to extract a core pathological response signature. Early changes at 24 h post-dose in AST, ALT, total protein, and calcium demonstrated strong predictive value for 48-h toxicity profiles (AUROC 0.98), underscoring the translational potential of early biomarkers. This study highlights both the robustness and contextual limitations of clinical chemistry data in toxicological studies. It underscores the importance of matched-control designs and multivariate approaches for multisite studies and advocates for the integration of early predictive modelling to optimise study design and align with the principles of the Replace, Reduce, and Refine initiative.

Unprecedented Burning in Tropical Peatlands During the 20th Century Compared to the Previous Two Millennia - Yuwan Wang; Ted R. Feldpausch; Graeme T. Swindles; Patrick Moss; Hamish A. McGowan; Thomas G. Sim; Paul J. Morris; Adam Benfield; Colin Courtney‐Mustaphi; David Wahl; Encarni Montoya; Esther Githumbi; et al. (Global Change Biology, 2026)
Tropical peatland wildfire incidence has risen in recent decades, driven by drainage for land use and intensified by severe droughts with global climate change. These disturbances have altered vegetation structure, disrupted ecosystem functioning, and increased carbon emissions, particularly in Southeast Asia. However, the long‐term history and characteristics of wildfires in tropical peatlands remain largely unknown. Here, we compiled fifty‐eight macro‐charcoal records from peatlands across the tropics, ranging from lowland forested to montane peatlands, to assess millennia‐scale changes and controlling factors of tropical peatland burning. We divided the datasets into four main sub‐regions: Neotropical, Afrotropical, Indomalayan and Australasian ecoregions to explore regional variability. Tropical peatlands had high burning levels between 0 and 850 ce , followed by a relatively low and stable period until a marked increase during the 20th century. The general trend in tropical peatland burning follows changes in global temperature, and climate variables that control the length and severity of drought events have a notable influence on peat burning before 1900 ce . During the 20th century, regional differences were observed, with declining fire trends in the Neotropical and Afrotropical regions and increasing fire trends in the Indomalayan and Australasian regions. This difference is likely attributable to human activities, and such intervention is also evident in palm swamps and hardwood swamps under similar wet, weakly seasonal climates. With the increase in anthropogenic pressures on peatlands and greater climate variability, future wildfires in peatlands are likely to become more frequent and widespread across all tropical ecoregions. Conservation and sustainable land‐use practices could be used to mitigate and control peatland burning and protect these carbon‐rich sinks.

Genetic marker type impacts ex situ conservation minimum sample size estimates and their variance - Austin C. Koontz; Gavin D. Salas; Sean M. Hoban (Conservation Genetics, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

First detection of Babesia spp. in Amblyomma mixtum from Veracruz, Mexico - Pamela Aguilar-Meraz; Sokani Sánchez-Montes; Ana C. Montes de Oca-Aguilar; Kevin J. Olivares-Calles; Estefanía Grostieta; Carlos I. Miranda Caballero; Amalia Cabrera-Núñez; Dora Romero-Salas; Anabel Cruz-Romero; Mariel Aguilar-Domínguez (Tropical Animal Health and Production, 2026)

Tropical Montane Cloud Forests Have High Resilience to Five Years of Severe Soil Drought - David C. Bartholomew; Paulo R. L. Bittencourt; Darcy Galiano Cabrera; Roxana Sacatuma Cruz; Jimmy R. Chambi Paucar; Daniela Corrales Alvarez; Eric Cosio; Blanca Espinoza Otazu; Darwin Manuel Mamani; Patrick Meir; George A. Muñoz Hermoza; Rafael S. Oliveira; et al. (Global Change Biology, 2026)
Tropical montane cloud forests (TMCFs) are globally important ecosystems, acting as large carbon sinks and supporting exceptional biodiversity. However, climate‐driven declines in rainfall threaten these forests, but their responses to long‐term soil moisture deficit remain poorly understood. We implemented a 5‐year throughfall exclusion (TFE) experiment in a Peruvian TMCF, reducing soil moisture by 69.1% across a 0.09 ha plot. We compared the full carbon cycle budget, and surveyed tree physiological traits linked to hydraulics, metabolism and nutrients in the TFE plot and an adjacent, unmodified control (CON) plot. Soil drought reduced gross primary productivity by 4.24 ± 1.97 Mg C ha −1 year −1 but did not change net primary productivity because of an equivalent 3.38 ± 1.42 Mg C ha −1 year −1 decline in autotrophic respiration. Net ecosystem exchange also remained unchanged over 5 years of soil drought. Trees did not change xylem conductivity, hydraulic safety margins or photosynthetic capacity in the TFE, but did have 0.027 ± 0.011 g cm −3 denser wood and 4.58% ± 1.03% higher trunk starch concentrations. These results suggest that trees in TMCF avoid hydraulic failure and carbon starvation under sustained soil moisture drought via metabolic downregulation, resource conservation and non‐structural carbohydrate storage. However, reduced uptake of nutrients (nitrogen, phosphorus, calcium) and 90.6% ± 29.8% decline in fruit production may impact future growth and demography. Our findings demonstrate surprising resilience of TMCFs to sustained, severe soil drought but highlight potential impacts on nutrient cycling and reproduction under climate change. Understanding the impacts of soil drought in conjunction with other climatic changes (e.g., fog reduction, temperature increases) is needed to fully assess the resilience of TMCFs to climate change.

What is hidden in the distribution of sea cucumber faecal casts? Spatial point pattern analysis reveals tracemaker community competition in the Bering Sea abyssal plain - Olmo Miguez-Salas; Phillip C. Boan; Joséphine Pierrat (Progress in Oceanography, 2025)

Review of weighting methods for life cycle impact assessment under GLAM - Cecilia Askham; Rosalie Arendt; Till M. Bachmann; Luis C. Dias; Andrea Amadei; Laura Scherer; Hua Qian; Lea Rupcic; Bengt Steen; João Santos; Masaharu Motoshita; Breno Barros Telles do Carmo; et al. (The International Journal of Life Cycle Assessment, 2025)
Purpose Weighting is the process of assigning relative importance to life cycle inventory results or indicator results across impact categories, using weighting factors based on value choices. It is an optional step within Life Cycle Assessment (LCA) but plays an important role in interpreting and communicating the relative importance of different environmental impacts. As part of the Global LCIA Guidance (GLAM) project under the UN Life Cycle Initiative, a comprehensive review of weighting methods was conducted to better understand which approaches are most appropriate for different applications in LCA. Methods Members of the GLAM weighting subtask identified and reviewed twenty-seven weighting methods. These methods were grouped into four categories: Multiple Criteria Decision Analysis (MCDA), monetary, data-driven and distance-to-target methods. Classifiers based on inherent features of the weighting methods were applied to support their inclusion or exclusion from further considerations. Each method then was assessed against a set of evaluation criteria defined by the subtask members. A color-code system (green, yellow or red) was applied to indicate the degree to which each method met each criterion to facilitate comparison and communication. Results and discussion Each method was briefly described with appropriate references, including examples of usage in LCA studies where available. The review results are summarized in a table that highlights the performance of each method against the evaluation criteria. All monetary methods are classified as trade-off rates, whereas there are MCDA methods and data-driven methods that can be either trade-off rates or importance coefficients. All distance-to-target methods are classified as importance coefficients. The ability of each method to incorporate temporal discounting or cultural differentiation varies, depending on the data availability and study design. None of the methods reviewed fully met all evaluation criteria, especially within the scope of the GLAM project. Some criteria (like Scientific validity) are sufficiently met by almost all of these methods. Conclusions Existing weighting methods based on different approaches have both advantages and limitations. No single method is universally sufficient, and their validity depends on context. This comprehensive overview of available weighting methods provides a valuable starting point for practitioners seeking to identify suitable weighting method for specific LCA applications. To facilitate easy use, a software was also developed based on this review to support the selection of the most appropriate weighting method for LCA studies.

Epigenetic regulation of TIMP-3 expression in human macrophages via physiological and pharmacological modification of histone3 lysine27 (H3K27) - Gökçe Yıldırım-Buharalıoğlu; Graciela B. Sala-Newby; Mark Bond; Andrew C. Newby (Molecular Biology Reports, 2025)

Inclusion of black soldier fly (Hermetia illucens) larvae frass as an alternative protein source in the diet of Florida native yearling ewes - Britany M. Fernandez-Mora; J.A. Arce-Cordero; C. NinoDeGuzman; G.K. Salas-Solis; K.G. Arriola; K.E. Sullivan; D. Vyas (Animal Feed Science and Technology, 2025)

Delayed embryonic attachment, circulating pregnancy-associated glycoproteins, and pregnancy loss in heifer embryo recipients - João Paulo N. Andrade; Rafael R. Domingues; Victor E. Gomez-León; Guilherme Madureira; Luma C. Sartori; Gustavo F. Grillo; Meliton Fosado; Rodrigo V. Sala; Milo C. Wiltbank (Theriogenology, 2025)

It's not all about PFAS: Metal(loid)s are associated with physiological and metabolic changes in a native frog from conservation wetlands - Damian C. Lettoof; Rui Wang; Brad Clarke; Nicola Gray; Samuele Sala; Nick Bourne; William R. Richmond; Helen E. Nice; Peter Novak; Brenton von Takach; Bruce L. Webber; Anna H. Kaksonen; et al. (Environmental Pollution, 2025)

Biotechnological valorisation of Spent Automotive Catalytic Converters: Marine microorganisms in PGE leaching and recovery - L. Vitale; P. Tedesco; C. Galasso; G.A. Vitale; G. Varola; G. Della Sala; F. Palma Esposito; S. Balzano; J. Ghani; D. de Pascale; E. Dinelli; T.C. Meisel; et al. (Journal of Environmental Chemical Engineering, 2025)

Role of Epithelial-Mesenchymal Transition in Sunitinib-induced metastatic dissemination in a xenograft orthotopic triple-negative breast cancer mouse model - L. Sala; G. Dellavedova; L. Bertola; G. Magani; A. Mangoni; S. Tommasi; J. Hulin; C. Ghilardi; C. Recordati (Journal of Comparative Pathology, 2025)

Drug-induced polyploid giant cancer cells in a preclinical model of high grade serous ovarian cancer - L. Bertola; L. Sala; P. Roccabianca; P. Riccaboni; A. Capuano; S. Muzzin; I. Pellarin; F. Basso-Valentina; G. Baldassarre; C. Lenardi; C. Perego; E. Scanziani; et al. (Journal of Comparative Pathology, 2025)

Ovarian superstimulation for in vitro embryo production based on Anti-Müllerian hormone phenotype: Effect of FSH dose schedule - Jessica C.L. Motta; Rodrigo V. Sala; Cameron B. Hayden; Daniela C. Pereira; Vanessa C. Fricke; Victor A. Absalón-Medina; Pablo J. Ross; Alvaro García-Guerra (Animal Reproduction Science, 2025)

Uptake and translocation of microplastics from sewage sludge by the fern Pteris vittata - Davide Marzi; Andrea C. Sala-Navarro; Maria Luisa Antenozio; Sara Michetti; Cristina Caissutti; Rosita Marabottini; Ana Beltran Sanahuja; Carlos Sanz-Lazaro; Patrizia Brunetti (Journal of Environmental Management, 2025)

COVID-19 pandemic exacerbated food insecurity in South American countries - Carlos Frederico A. Vasconcelos-Neto; Michelle Jacob; Daniel Tregidgo; Denis Valle; Hani R. El Bizri; Sávio Marcelino Gomes; Julia E. Fa; Thais Q. Morcatty; Frederico Ozanan Barros Monteiro; Alessandra Scofield; Alessandra Matte; Willandia A. Chaves; et al. (Food Security, 2025)
The COVID-19 pandemic triggered unparalleled political, economic, and social ramifications, exacerbating global food insecurity (FI). To understand the overall impact of the pandemic and how different socio-economic groups were affected, we assessed prevalence and severity of FI in a sample of 18,997 households across seven countries in South America. We employed the Food Insecurity Experience Scale developed by the FAO. Our results showed that pre-pandemic, 4.5% of the sampled population across the entire continent faced Moderate FI, while 0.6% experienced severe FI. During the pandemic, Moderate FI increased to 16.9% (+ 12.4%), and Severe FI to 2.7% (+ 2.1%). By country, pre-pandemic households in Venezuela had the highest prevalence of Moderate FI (9.7%), with Peru experiencing the highest Severe FI frequency (1.1%). Peru had the greatest rise in Moderate (+ 23.9%) and Severe FI (+ 4.6%) during the pandemic. Low-income households, defined as those earning < 2 minimum wages per month, were most susceptible to FI. Uruguayan low-income families exhibited the most significant rise (+ 40.4%) in Moderate FI, while those in Peru experienced an increase of + 9.1% in Severe FI. This study measures the profound and far-reaching impact of the COVID-19 pandemic on FI in South America. Our findings also emphasise the critical importance of implementing effective public policy interventions to improve resilience against future shocks. This would enable policymakers to develop targeted strategies that address the immediate challenges posed by pandemics as well as laying the groundwork for a more resilient and sustainable food security landscape in the region.

Changes in macrozoobenthic assemblages of a coastal lagoon in the context of long-term human pressures and a eutrophication process - A. Sala-Mirete; C. Marcos; M. Vicente-Ríos; O. Sánchez-Fernández; J. Texier; A. Pérez-Ruzafa (Marine Environmental Research, 2025)

How adverse are Mediterranean waters to the deep-sea fauna? A study of the Gibraltar exchange based on Mollusca from the “BALGIM” expedition - Utrilla O; Gofas S; Salas C (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

A clinical chemical atlas of xenobiotic toxicity for the Sprague–Dawley rat - Janonna Kadyrov; Samuele Sala; Lucy Grigoroff; Novia Minaee; Reika Masuda; Samantha Lodge; Timothy M. Ebbels; Michael D. Reily; Donald Robertson; Lois Lehman-McKeeman; John Shockcor; Bruce D. Car; et al. (Archives of Toxicology, 2025)
The Consortium for Metabonomic Toxicology (COMET) studies was designed to model metabolic responses to organ- and mechanism-specific toxins to predict acute drug toxicity in rats. A range of clinical chemical parameters were measured in 7-day toxicology studies for 86 toxins eliciting a range of organ- and mechanism-specific effects. Additionally, 21 surgical or physiological stressors were evaluated to identify physiological or metabolic responses that might confound the interpretation of observed toxicity profiles. From these studies on a total of 3473 rats measured at six pharmaceutical companies, we provide a set of 12 serum and 5 urine physical and clinical chemistry parameters. Samples were collected at 24 h, 48 h and 168 h post-dose for each animal and are presented as a downloadable database file. We also summarise the main observations based on the group response at the level of the individual toxin. We demonstrate that correlations between parameters, such as serum bilirubin and aspartate aminotransferase (AST), provide a more nuanced profile of organ-specific toxicity than consideration of individual parameters alone. In addition, we highlight the variability in the measured parameters across the dataset attributable to inter-laboratory differences, and the heterogeneity of metabolic responses to particular compounds or differences in temporal patterns of response. This clinical chemistry atlas of toxicity serves as a valuable reference tool for evaluating the potential toxicity of novel drug candidates.

Archaeointensity study of pottery from the Maya settlements of La Blanca and Chilonché (Petén, Guatemala): New data to constrain the geomagnetic field evolution in Central America - M. Gómez-Paccard; A. Chauvin; R. Bonilla-Alba; C. Vidal-Lorenzo; M. Salas (Physics of the Earth and Planetary Interiors, 2025)

Biocrust Mosses and Cyanobacteria Exhibit Distinct Carbon Uptake Responses to Variations in Precipitation Amount and Frequency - Kristina E. Young; Osvaldo Sala; Anthony Darrouzet‐Nardi; Colin Tucker; Rebecca Finger‐Higgens; Megan Starbuck; Sasha C. Reed (Ecology Letters, 2025)
Dryland organisms exhibit varied responses to changes in precipitation, including event size, frequency, and soil moisture duration, influencing carbon uptake and reserve management strategies. This principle, central to the pulse‐reserve paradigm, has not been thoroughly evaluated in biological soil crusts (biocrusts), essential primary producers on dryland surfaces. We conducted two experiments to investigate carbon uptake in biocrusts under different precipitation regimes. In the first, we applied a gradient of watering amounts to biocrusts dominated by moss or cyanobacteria, hypothesising distinct pulse‐response strategies. The second experiment extended watering treatments over three months, varying pulse size and frequency. Our results revealed distinct carbon uptake patterns: moss crusts exhibited increased CO 2 uptake with larger, less frequent watering events, whereas cyanobacteria crusts maintained similar carbon uptake across all event sizes. These findings suggest divergent pulse‐response strategies across biocrust types, with implications for modelling dryland carbon dynamics and informing land management under changing precipitation regimes.

ReBreed21-ET: Evaluation of a rapid resynchronization program that allows timed embryo transfer every 21 days - João Paulo N. Andrade; Victor E. Gomez-León; Guilherme Madureira; Luma C. Sartori; Gustavo F. Grillo; Rafael R. Domingues; Meliton Fosado; Rodrigo V. Sala; Milo C. Wiltbank (Theriogenology, 2025)

Pericardium decellularization in a one-day, two-step protocol - P. López-Chicón; J. I. Rodríguez Martínez; C. Castells-Sala; L. Lopez-Puerto; L. Ruiz-Ponsell; O. Fariñas; A. Vilarrodona (Molecular and Cellular Biochemistry, 2025)

Evaluation of intra- and inter-rater agreement on ultrasound measurements of dairy cow teats by operators with different experience levels - I. Nocera; G. Sala; C. Orsetti; J. M. Rodriguez-Lopez; M. Sgorbini; F. Bonelli (Veterinary Research Communications, 2025)

Assessments of expected MPA outcomes can inform and improve biodiversity conservation: Case studies using The MPA Guide - Jenna Sullivan-Stack; Gabby N. Ahmadia; Dominic A. Andradi-Brown; Alexandra Barron; Cassandra M. Brooks; Joachim Claudet; Barbara Horta e Costa; Estradivari; Laurel C. Field; Sylvaine Giakoumi; Emanuel Gonçalves; Natalie Groulx; et al. (Marine Policy, 2024)

Toxicity of crude oil-derived polar unresolved complex mixtures to Pacific herring embryos: Insights beyond polycyclic aromatic hydrocarbons - Maxwell L. Harsha; Yanila Salas-Ortiz; Alysha D. Cypher; Ed Osborn; Eduardo Turcios Valle; Jacob L. Gregg; Paul K. Hershberger; Yuri Kurerov; Sarah King; Aleksandar I. Goranov; Patrick G. Hatcher; Anastasia Konefal; et al. (Science of The Total Environment, 2024)

Novel microsatellite markers suggest significant genetic isolation in the Eastern Pacific sponge Aplysina gerardogreeni - Manuel Ricardo Salas-Castañeda; Nancy C. Saavedra-Sotelo; José Antonio Cruz-Barraza; Celia Isabel Bisbal-Pardo; Axayácatl Rocha-Olivares (Molecular Biology Reports, 2024)
Background The Eastern Tropical Pacific (ETP) harbors a great diversity of Porifera. In particular, the Aplysina genus has acquired biotechnological and pharmacological importance. Nevertheless, the ecological aspects of their species and populations have been poorly studied. Aplysina gerardogreeni is the most conspicuous verongid sponge from the ETP, where it is usually found on rocky-coralline ecosystems. We evaluated the polymorphism levels of 18 microsatellites obtained from next-generation sequencing technologies. Furthermore, we tested the null hypothesis of panmixia in A. gerardogreeni population from two Mexican-Pacific localities. Methods and results A total of 6,128,000 paired reads were processed of which primer sets of 18 microsatellites were designed. The loci were tested in 64 specimens from Mazatlan, Sinaloa (N = 32) and Isabel Island, Nayarit (N = 32). The microsatellites developed were moderately polymorphic with a range of alleles between 2 and 11, and Ho between 0.069 and 0.785. Fifteen loci displayed significant deviation from the Hardy–Weinberg equilibrium. No linkage disequilibrium was detected. A strong genetic structure was confirmed between localities using hierarchical Bayesian analyses, principal coordinates analyses, and fixation indices ( F ST = 0.108*). All the samples were assigned to their locality; however, there was a small sign of mixing between localities. Conclusions Despite the moderate values of diversity in microsatellites, they showed a strong signal of genetic structure between populations. We suggest that these molecular markers can be a relevant tool to evaluate all populations across the ETP. In addition, 17 of these microsatellites were successfully amplified in the species A. fistularis and A. lacunosa , meaning they could also be applied in congeneric sponges from the Caribbean Sea. The use of these molecular markers in population genetic studies will allow assessment of the connectivity patterns in species of the Aplysina genus.

Upregulation of the canonical signaling pathway of interferon-gamma is associated with glioblastoma progression - Sayra Ximena Zamora-Salas; Marina Macías-Silva; Angeles C. Tecalco-Cruz (Molecular Biology Reports, 2024)

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

The biophysical dynamics of giant kelp, Macrocystis pyrifera : Seasonal patterns and dispersal mechanisms in the southeast Pacific - G. Thompson‐Saud; A. Grech; S. Choukroun; S. I. Vásquez; C. Salas; A. Ospina‐Alvarez (Journal of Biogeography, 2024)
Aim Dispersal and connectivity play important roles in shaping the population structure of giant kelp, Macrocystis pyrifera , across the western coast of South America. Its high potential dispersal capacity suggests the existence of metapopulations, where discrete habitat patches or groups of patches form subpopulations that interact at some level. However, the dispersal patterns of giant kelp in this region have not been quantified. This study assesses the dispersal and settlement of Macrocystis pyrifera in the southeast Pacific, specifically focusing on the impact of environmental variables and ocean currents within the Humboldt Current System. Location Southeast Pacific (coast of Chile and Peru). Time Period 1997–2008. Major Taxa Studied Macrocystis pyrifera (giant kelp). Methods Using a combination of hydrodynamic and individual‐based models, we analysed kelp fragment movements over 12 years, with a particular emphasis on the effects of the El Niño‐Southern Oscillation (ENSO) and seasonal changes. Results Our results highlight a key settlement area in the southern Chilean region. We found that shorter travel distances of kelp fragments increased the likelihood of reaching a suitable habitat, underscoring the importance of local environmental conditions. We delineated intricate northward dispersal paths for kelp fragments, which appear to be governed by the interplay of wind and ocean current dynamics. Seasonal variations, notably in autumn and winter, favour the likelihood of reaching a settlement area due to favourable winds. Furthermore, ENSO events appear to influence dispersal distances, with fragments travelling the longest distances during El Niño phases. Main Conclusion These findings are essential for informing kelp conservation strategies in the context of climate change, emphasizing the necessity of considering local and seasonal environmental factors alongside ENSO impacts.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

P06-20 OMICs approaches linking effects of endocrine disrupters on developing rat hippocampus with impaired memory function in adult offspring and human stem cell-derived in vitro models - W. Lichtensteiger; C. Bassetti-Gaille; H. Rehrauer; N. Caporale; B. Linillos Pradillo; L. Rancan; H. Idrissi; L. Miguélez-Salas; J. Felix; S.D. Paredes; S. Evangelista; M. de la Fuente; et al. (Toxicology Letters, 2024)

Understanding the risks of co-exposures in a changing world: a case study of dual monitoring of the biotoxin domoic acid and Vibrio spp. in Pacific oyster - Alle A. Y. Lie; Amity G. Zimmer-Faust; Rachel E. Diner; Emily Kunselman; Zachary Daniel; Kathryn Van Artsdalen; Mariana C. Salas Garcia; Jack A. Gilbert; Dana Shultz; Jeff Chokry; Kylie Langlois; Jayme Smith (Environmental Monitoring and Assessment, 2024)

Infection with different Neospora caninum strains causes differences in the glycosylation pattern in the uteri and placentae of Neospora caninum-infected heifers - Sergio G. Caspe; Jose L. Konrad; Dadin P. Moore; Juan M. Sala; Paola Della-Rosa; Luis M. Ortega-Mora; Diana R. Bacigalupe; Maria C. Venturini; Carlos M. Campero; Claudio G. Barbeito (Journal of Comparative Pathology, 2024)

Multiple criteria decision analysis to support the design of safe and sustainable chemicals and materials - Luis C. Dias; Carla Caldeira; Serenella Sala (Science of The Total Environment, 2024)

Artificial Light at Night Reduces Flashing in Photinus and Photuris Fireflies During Courtship and Predation - Juan S. Hillón-Salas; Juan D. Pineda-Dueñas; Ana M. Romero-Chacón; Juliana Fonseca-Tellez; Manuela Cardona-Restrepo; Sofía C. Garrido-Villegas; Diego Mejía-Tovar; Camilo Arenas-Ríos; Laia Gaitán-Botero; Zulma S. Barón-Garzón; Andrés F. Robayo-Salek; Harold Pulido-Guarín; et al. (Journal of Insect Behavior, 2024)
Artificial light at night (ALAN) affects species-specific communication in a wide range of nocturnal species, including fireflies (Lampyridae). Fireflies rely on bioluminescent signals for communicating. In this study, we conducted two manipulative field experiments to evaluate the effect of artificial light at night on the flashing activity of male and female neotropical fireflies during courtship and predation. Our results showed a significant reduction in the flashing activity of both males and females exposed to ALAN during courtship and predation. Remarkably, the effect of ALAN on male flashing activity seems to be independent of female flashing activity. In conclusion, ALAN disrupts bioluminescent intraspecific (courtship) and interspecific (predation) communication, which in turn could influence mating success, thus negatively affecting neotropical firefly populations in the long term. Our findings contribute to understanding the challenges faced by neotropical firefly communities in the presence of ALAN.

Last twenty-years activity of cardiovascular tissue banking in Barcelona - C. Castells-Sala; M. L. Pérez; E. Agustí; A. Aiti; E. Tarragona; A. Navarro; J. Tabera; O. Fariñas; J. L. Pomar; A. Vilarrodona (Cell and Tissue Banking, 2024)
The Barcelona Tissue Bank was established from the merge of two previous multi-tissue banks. Potential donors are screened by Donor Center staff and multi-tissue retrieval is performed by specialized own teams. Tissue processing and preservation is performed in clean room facilities by specialised personnel. After quality control of both donor and all tissues results, the heart valves and vascular segments are stored until medical request. The aim of this report is to present the cardiovascular tissue activity and retrospectively evaluate the outcomes of the changes performed in last 20 years. Cardiovascular tissue from 4088 donors was received, specifically 3115 hearts and 2095 vascular segments were processed and evaluated. A total of 48% of the aortic valves, 68% of the pulmonary valves and 75% of the vascular segments were suitable for transplant. The main reason for discarding tissue was macroscopic morphology followed by microbiological results, for both valves and arteries. Altogether, 4360 tissues were distributed for transplantation: 2032 (47%) vascular segments, 1545 (35%) pulmonary valves and 781 (18%) aortic valves. The most common indication for aortic valve surgery was the treatment of endocarditis, while for pulmonary valves, it was congenital malformation reconstruction. Vascular segments were mainly used for reconstruction after ischemia. During this period, a number of changes were made with the goal of enhancing tissue quality, safety and efficacy. These improvements were achieved through the use of a new antibiotic cocktail, increasing of donor age criteria and changing the microbiological control strategy.

Global patterns and environmental drivers of forest functional composition - Elise Bouchard; Eric B. Searle; Pierre Drapeau; Jingjing Liang; Javier G. P. Gamarra; Meinrad Abegg; Giorgio Alberti; Angelica Almeyda Zambrano; Esteban Alvarez‐Davila; Luciana F. Alves; Valerio Avitabile; Gerardo Aymard; et al. (Global Ecology and Biogeography, 2024)
Aim To determine the relationships between the functional trait composition of forest communities and environmental gradients across scales and biomes and the role of species relative abundances in these relationships. Location Global. Time period Recent. Major taxa studied Trees. Methods We integrated species abundance records from worldwide forest inventories and associated functional traits (wood density, specific leaf area and seed mass) to obtain a data set of 99,953 to 149,285 plots (depending on the trait) spanning all forested continents. We computed community‐weighted and unweighted means of trait values for each plot and related them to three broad environmental gradients and their interactions (energy availability, precipitation and soil properties) at two scales (global and biomes). Results Our models explained up to 60% of the variance in trait distribution. At global scale, the energy gradient had the strongest influence on traits. However, within‐biome models revealed different relationships among biomes. Notably, the functional composition of tropical forests was more influenced by precipitation and soil properties than energy availability, whereas temperate forests showed the opposite pattern. Depending on the trait studied, response to gradients was more variable and proportionally weaker in boreal forests. Community unweighted means were better predicted than weighted means for almost all models. Main conclusions Worldwide, trees require a large amount of energy (following latitude) to produce dense wood and seeds, while leaves with large surface to weight ratios are concentrated in temperate forests. However, patterns of functional composition within‐biome differ from global patterns due to biome specificities such as the presence of conifers or unique combinations of climatic and soil properties. We recommend assessing the sensitivity of tree functional traits to environmental changes in their geographic context. Furthermore, at a given site, the distribution of tree functional traits appears to be driven more by species presence than species abundance.

A global assessment of environmental and climate influences on wetland macroinvertebrate community structure and function - Luis B. Epele; Emilio A. Williams‐Subiza; Matthew S. Bird; Aurelie Boissezon; Dani Boix; Eliane Demierre; Conor G. Fair; Patricia E. García; Stephanie Gascón; Marta G. Grech; Hamish S. Greig; Michael Jeffries; et al. (Global Change Biology, 2024)
Estimating organisms' responses to environmental variables and taxon associations across broad spatial scales is vital for predicting their responses to climate change. Macroinvertebrates play a major role in wetland processes, but studies simultaneously exploring both community structure and community trait responses to environmental gradients are still lacking. We compiled a global dataset (six continents) from 756 depressional wetlands, including the occurrence of 96 macroinvertebrate families, their phylogenetic tree, and 19 biological traits. Using Bayesian hierarchical joint species distribution models (JSDMs), we estimated macroinvertebrate associations and compared the influences of local and climatic predictors on both individual macroinvertebrate families and their traits. While macroinvertebrate families were mainly related to broad‐scale factors (maximum temperature and precipitation seasonality), macroinvertebrate traits were strongly related to local wetland hydroperiod. Interestingly, macroinvertebrate families and traits both showed positive and negative associations to the same environmental variables. As expected, many macroinvertebrate family occurrences were positively associated with temperature, but a few showed the opposite pattern and were found in cooler or montane regions. We also found that wetland macroinvertebrate communities would likely be affected by changing climates through alterations in traits related to precipitation seasonality, temperature seasonality, and wetland area. Temperature increases may negatively affect collector and shredder functional groups. A decrease in precipitation could lead to reductions in wetland area benefiting drought‐tolerant macroinvertebrates, but it may negatively affect macroinvertebrates lacking those adaptations. Wetland processes may be compromised through broad‐scale environmental changes altering macroinvertebrate family distributions and local hydroperiod shifts altering organism traits. Our complementary family‐based and trait‐based approaches elucidate the complex effects that climate change may produce on wetland ecosystems.

Intra-urban variability of long-term exposure to PM2.5 and NO2 in five cities in Colombia - Laura A. Rodriguez-Villamizar; Yurley Rojas; Sara Grisales; Sonia C. Mangones; Jhon J. Cáceres; Dayana M. Agudelo-Castañeda; Víctor Herrera; Diana Marín; Juan G. Piñeros Jiménez; Luis C. Belalcázar-Ceron; Oscar Alberto Rojas-Sánchez; Jonathan Ochoa Villegas; et al. (Environmental Science and Pollution Research, 2023)
Rapidly urbanizing cities in Latin America experience high levels of air pollution which are known risk factors for population health. However, the estimates of long-term exposure to air pollution are scarce in the region. We developed intraurban land use regression (LUR) models to map long-term exposure to fine particulate matter (PM 2.5 ) and nitrogen dioxide (NO 2 ) in the five largest cities in Colombia. We conducted air pollution measurement campaigns using gravimetric PM 2.5 and passive NO 2 sensors for 2 weeks during both the dry and rainy seasons in 2021 in the cities of Barranquilla, Bucaramanga, Bogotá, Cali, and Medellín, and combined these data with geospatial and meteorological variables. Annual models were developed using multivariable spatial regression models. The city annual PM 2.5 mean concentrations measured ranged between 12.32 and 15.99 µg/m 3 while NO 2 concentrations ranged between 24.92 and 49.15 µg/m 3 . The PM 2.5 annual models explained 82% of the variance ( R 2 ) in Medellín, 77% in Bucaramanga, 73% in Barranquilla, 70% in Cali, and 44% in Bogotá. The NO 2 models explained 65% of the variance in Bucaramanga, 57% in Medellín, 44% in Cali, 40% in Bogotá, and 30% in Barranquilla. Most of the predictor variables included in the models were a combination of specific land use characteristics and roadway variables. Cross-validation suggests that PM 2.5 outperformed NO 2 models. The developed models can be used as exposure estimate in epidemiological studies, as input in hybrid models to improve personal exposure assessment, and for policy evaluation.

Basic human values drive food choice decision-making in different food environments of Kenya and Tanzania - Christine E. Blake; Eva C. Monterrosa; Krystal K. Rampalli; Abdullah Nurus Salam Khan; Ligia I. Reyes; Shiny Deepika Drew; Paula Dominguez-Salas; Salome A. Bukachi; Mariah Ngutu; Edward A. Frongillo; Elyse Iruhiriye; Amy Webb Girard (Appetite, 2023)

P08-19: Transcriptomics in Developing Rat Hippocampus Perinatally Exposed to Environmental Endocrine Active Chemicals and Impaired Memory Function in Adult Offspring: Convergence of Chemical Actions on Common Signalling Pathways - W. Lichtensteiger; C. Bassetti-Gaille; H. Rehrauer; J. Felix Escalera; B. Linillos-Pradillo; H. Idrissi; L. Miguéles-Salas; L. Rancan; S. Evangelista; M. De La Fuente; P. Leonards; S. Paredes; et al. (Toxicology Letters, 2023)

Modelling the effect of the tidal cycle on the high phytoplankton biomass area of Cape Trafalgar (SW Iberian Peninsula) - Iria Sala; Sergio M. Vallina; Marina Lévy; Marina Bolado-Penagos; Carlos M. García; Fidel Echevarría; José C. Sánchez-Garrido (Progress in Oceanography, 2023)

Late Pleistocene boreal molluscs in the Gulf of Cadiz: Past and current oceanographic implications - J. Urra; O. Utrilla; S. Gofas; V.A. Valencia; C. Farias; E. González-García; N. López-González; L.M. Fernández-Salas; J.L. Rueda (Quaternary Science Reviews, 2023)

Towards recycling of waste carbon fiber: Strength, morphology and structural features of recovered carbon fibers - A. Salas; M.E. Berrio; S. Martel; A. Díaz-Gómez; Daniel A. Palacio; V. Tuninetti; C. Medina; M.F. Meléndrez (Waste Management, 2023)

Wild pigs and their widespread threat to biodiversity conservation in South America - Luciano F. La Sala; Julián M. Burgos; Nicolás C. Caruso; Camilo E. Bagnato; Sebastián A. Ballari; Demetrio L. Guadagnin; Andreas Kindel; Matheus Etges; Mariano L. Merino; Andrea Marcos; Oscar Skewes; Daniella Schettino; et al. (Journal for Nature Conservation, 2023)

The Complete Mitogenome of Amazonian Hyphessobrycon heterorhabdus (Characiformes: Characidae) as a Valuable Resource for Phylogenetic Analyses of Characidae - Luciano Fogaça de Assis Montag; Ricardo Koroiva; Ândrea Ribeiro-dos-Santos; Leandro Magalhães; Giovanna C. Cavalcante; Caio S. Silva; Sávio Guerreiro; Daniel H. F. Gomes; Jorge E. S. de Souza; Sandro J. de Souza; Lidia Brasil Seabra; Maria Dayanne Lima de Lucena; et al. (Fishes, 2023)
Hyphessobrycon heterorhabdus (Ulrey, 1894), popularly known as ‘Flag Tetra’ in English speaking countries, belongs to the genus Hyphessobrycon of the family Characidae, and is widely present in the eastern Amazon basin. Here, using Illumina sequencing, we report the complete mitogenome sequence of H. heterorhabdus. Overall, the mitogenome has 17,021 bp, containing 13 protein-coding, 22 tRNA, and 2 rRNA genes. Non-ambiguous nucleotide compositions of the H. heterorhabdus mitogenome are A: 29.2%, T: 29.4%, G: 15.6%, and C: 25.8%. As recently indicated, the phylogenetic analyses did not support four separate genera (Hemigrammus, Hyphessobrycon, Moenkhausia, and Psalidodon) of Characidae. Understanding the H. heterorhabdus mitogenome is important for taxonomic purposes as well as for the molecular characterization of environmental pollutants. Thus, the mitogenome described here will be a valuable resource for studies on environmental changes, evolutionary genetics, species delimitation, and phylogenetic analyses in Characidae.

Regional variability in peatland burning at mid-to high-latitudes during the Holocene - Thomas G. Sim; Graeme T. Swindles; Paul J. Morris; Andy J. Baird; Angela V. Gallego-Sala; Yuwan Wang; Maarten Blaauw; Philip Camill; Michelle Garneau; Mark Hardiman; Julie Loisel; Minna Vӓliranta; et al. (Quaternary Science Reviews, 2023)

First assessment of debris pollution in the gastrointestinal content of juvenile Magellanic penguins (Spheniscus magellanicus) stranded on the west south Atlantic coasts - Tatiana Recabarren-Villalón; Ana C. Ronda; Luciano La Sala; Cristina Sanhueza; Lucrecia Díaz; Lucas S. Rodríguez Pirani; A. Lorena Picone; Rosana M. Romano; Pablo Petracci; Andrés H. Arias (Marine Pollution Bulletin, 2023)

Biogeographic origins and drivers of alien plant invasions in the Canary Islands - Javier Morente‐López; Yurena Arjona; Marcos Salas‐Pascual; J. Alfredo Reyes‐Betancort; Marcelino J. del Arco‐Aguilar; Brent C. Emerson; Antonio García‐Gallo; Louis S. Jay‐García; Agustín Naranjo‐Cigala; Jairo Patiño (Journal of Biogeography, 2023)
Aim Understanding the historical and contemporaneous drivers of invasion success in island systems can decisively contribute to identifying sources and pathways that are more likely to give rise to new invaders. Based on a floristic‐driven approach, we aimed at determining the origins of the invasive alien flora of the Canary Islands and shedding light in the mechanisms shaping their distribution within the archipelago. Location Canary Islands. Taxon Vascular plants. Methods An updated checklist of the invasive alien flora of the Canary Islands was assembled along with complementary information related to the native biogeographical regions, stage of invasiveness and dates of naturalization. Statistical models were employed to describe differences in the number of species over space and time. We also used multivariate techniques to evaluate competing hypotheses related to the mechanisms driving invasive floristic composition within the archipelago. Results We provided a list of 149 alien plant species with a certain degree of invasiveness. The greatest number of invasive species originated from the Neotropics followed by the Cape Region, tropical Africa and the Mediterranean Basin. We observed a slow but steady increase in numbers of invasive species until the 1950s, followed by a stronger rise thereafter. In order to explain composition dissimilarity of the invasive flora among islands, a climatic matching hypothesis was fully supported, with geographic isolation and contemporary human‐mediated connectivity hypotheses receiving less and null support respectively. Main Conclusions We showed that the Neotropical region is the main source of plant invasions to the Canary Islands, outnumbering those from other regions with a Mediterranean‐type bioclimate. The assembly of the invasive flora within the archipelago appears to be driven primarily by climate, but with geographic distance also playing a role. This study calls for archipelago‐dependent assessments of the underlying mechanisms that contribute to plant invasion success within insular systems.

Highly selective recovery of Ni(II) in neutral and acidic media using a novel Ni(II)-ion imprinted polymer - A. Giove; Y. El Ouardi; A. Sala; F. Ibrahim; S. Hietala; E. Sievänen; C. Branger; K. Laatikainen (Journal of Hazardous Materials, 2023)

Trace classical conditioning impairment after lesion of the lateral part of the goldfish telencephalic pallium suggests a long ancestry of the episodic memory function of the vertebrate hippocampus - A. Gómez; B. Rodríguez-Expósito; F. M. Ocaña; C. Salas; F. Rodríguez (Brain Structure and Function, 2022)

PIWI-Interacting RNA (piRNA) and Epigenetic Editing in Environmental Health Sciences - Bambarendage P. U. Perera; Rachel K. Morgan; Katelyn M. Polemi; Kimmie E. Sala-Hamrick; Laurie K. Svoboda; Dana C. Dolinoy (Current Environmental Health Reports, 2022)

Factors associated with changes in exercise behaviors during the COVID-19 pandemic - Caroline Himbert; Cassandra A. Hathaway; Bailee Daniels; Karen Salas; Anjelica Ashworth; Biljana Gigic; Tengda Lin; Richard Viskochil; Anne C. Kirchhoff; Douglas Grossman; Jennifer Ose; Jonathan Tward; et al. (Cancer Causes & Control, 2022)

Recruitment dynamics and microhabitat selectivity of coral-reef fishes at three sites in the Mexican Caribbean - Villegas-Hernández H.; González-Salas C.; Guillén-Hernández S.; Poot-López G. (Environmental Biology of Fishes, 2022)

Estimating anisotropy directly via neural timeseries - Erik D. Fagerholm; W. M. C. Foulkes; Yasir Gallero-Salas; Fritjof Helmchen; Rosalyn J. Moran; Karl J. Friston; Robert Leech (Journal of Computational Neuroscience, 2022)
An isotropic dynamical system is one that looks the same in every direction, i.e., if we imagine standing somewhere within an isotropic system, we would not be able to differentiate between different lines of sight. Conversely, anisotropy is a measure of the extent to which a system deviates from perfect isotropy, with larger values indicating greater discrepancies between the structure of the system along its axes. Here, we derive the form of a generalised scalable (mechanically similar) discretized field theoretic Lagrangian that allows for levels of anisotropy to be directly estimated via timeseries of arbitrary dimensionality. We generate synthetic data for both isotropic and anisotropic systems and, by using Bayesian model inversion and reduction, show that we can discriminate between the two datasets – thereby demonstrating proof of principle. We then apply this methodology to murine calcium imaging data collected in rest and task states, showing that anisotropy can be estimated directly from different brain states and cortical regions in an empirical in vivo biological setting. We hope that this theoretical foundation, together with the methodology and publicly available MATLAB code, will provide an accessible way for researchers to obtain new insight into the structural organization of neural systems in terms of how scalable neural regions grow – both ontogenetically during the development of an individual organism, as well as phylogenetically across species.

Life-history traits facilitate the population success of the sergeant major Abudefduf saxatilis (Linnaeus, 1758, Perciformes: Pomacentridae) in the Caribbean Sea - H. Villegas-Hernández; E. Novelo-Ríos; K. Fuentes-Dantorie; S. Guillén-Hernández; C. González-Salas; D. Pech-Puch; R. Díaz-Gamboa; G. Poot-López (Marine Biology Research, 2022)

Empirical evidence on the effects of climate on the viability of common carp (Cyprinus carpio) populations in European lakes - A. T. Souza; C. Argillier; P. Blabolil; V. Děd; I. Jarić; A. P. Monteoliva; N. Reynaud; F. Ribeiro; D. Ritterbusch; P. Sala; M. Šmejkal; P. Volta; et al. (Biological Invasions, 2022)

Precipitation effects on nematode diversity and carbon footprint across grasslands - André L. C. Franco; Pingting Guan; Shuyan Cui; Cecilia M. de Tomasel; Laureano A. Gherardi; Osvaldo E. Sala; Diana H. Wall (Global Change Biology, 2022)
Free‐living nematodes are one of the most diverse metazoan taxa in terrestrial ecosystems and are critical to the global soil carbon (C) cycling through their role in organic matter decomposition. They are highly dependent on water availability for movement, feeding, and reproduction. Projected changes in precipitation across temporal and spatial scales will affect free‐living nematodes and their contribution to C cycling with unforeseen consequences. We experimentally reduced and increased growing season precipitation for 2 years in 120 field plots at arid, semiarid, and mesic grasslands and assessed precipitation controls on nematode genus diversity, community structure, and C footprint. Increasing annual precipitation reduced nematode diversity and evenness over time at all sites, but the mechanism behind these temporal responses differed for dry and moist grasslands. In arid and semiarid sites, there was a loss of drought‐adapted rare taxa with increasing precipitation, whereas in mesic conditions increases in the population of predaceous taxa with increasing precipitation may have caused the observed reductions in dominant colonizer taxa and yielded the negative precipitation–diversity relationship. The effects of temporal changes in precipitation on all aspects of the nematode C footprint (respiration, production, and biomass C) were all dependent on the site (significant spatial × temporal precipitation interaction) and consistent with diversity responses at mesic, but not at arid and semiarid, grasslands. These results suggest that free‐living nematode biodiversity and their C footprint will respond to climate change‐driven shifts in water availability and that more frequent extreme wet years may accelerate decomposition and C turnover in semiarid and arid grasslands.

Reverse thinking: taking a healthy diet perspective towards food systems transformations - I. D. Brouwer; M. J. van Liere; A. de Brauw; P. Dominguez-Salas; A. Herforth; G. Kennedy; C. Lachat; E. B. Omosa; E. F. Talsma; S. Vandevijvere; J. Fanzo; M. Ruel (Food Security, 2021)
Food systems that deliver healthy diets without exceeding the planet’s resources are essential to achieve the worlds’ ambitious development goals. Healthy diets need to be safe, accessible, and affordable for all, including for disadvantaged and nutritionally vulnerable groups such as of smallholder producers, traders, and consumers in low- and middle-income countries. Globally, food systems are experiencing rapid and drastic changes and are failing to fulfil these multiple duties simultaneously. The international community therefore calls for rigorous food systems transformations and policy solutions to support the achievement of healthy diets for all. Most strategies, however, are essentially supply- and market-oriented. Incorporation of a healthy diet perspective in food system transformation is essential to enable food systems to deliver not only on supplying nutritious foods but also on ensuring that consumers have access can afford and desire healthy, sustainable, and culturally acceptable diets. This paper argues that this should be guided by information on diets, dietary trends, consumer motives, and food environment characteristics. Transformational approaches and policies should also take into account the stage of food system development requiring different strategies to ensure healthier diets for consumers. We review current knowledge on drivers of consumer choices at the individual and food environment level with special emphasis on low- and middle income countries, discuss the converging and conflicting objectives that exist among multiple food-system actors, and argue that failure to strengthen synergies and resolve trade-offs may lead to missed opportunities and benefits, or negative unintended consequences in food system outcomes. The paper proposes a menu of promising consumer- and food-environment- oriented policy options to include in the food systems transformation agenda in order to shift LMIC consumer demand towards healthier diets in low- and middle income countries.

Dietary changes and food habits: social and clinical determinants in a cohort of women diagnosed with breast cancer in Barcelona (DAMA cohort) - C. Clotas; G. Serral; E. Vidal Garcia; R. Puigpinós-Riera; X. Bargalló; M. Domènec; M. Espinosa-Bravo; J. Grau; F. Macià; R. Manzanera; M. Pla; M. J. Quintana; et al. (Cancer Causes & Control, 2021)

Using the Red Band Difference Algorithm to Detect and Monitor a Karenia spp. Bloom Off the South Coast of Ireland, June 2019 - Catherine Jordan; Caroline Cusack; Michelle C. Tomlinson; Andrew Meredith; Ryan McGeady; Rafael Salas; Clynton Gregory; Peter L. Croot (Frontiers in Marine Science, 2021)
During the months of May, June, July and August 2019 the Red Band Difference algorithm was tested over Irish waters to assess its suitability for the Irish harmful algal bloom alert system. Over the 4 weeks of June an extensive localised surface phytoplankton bloom formed in the Celtic Sea, south of Ireland. Satellite imagery from the Sentinel-3a’s Ocean and Land Colour Instrument, processed using the Red Band Difference algorithm detected the bloom in surface shelf waters and helped monitor its movement. Daily satellite images indicated that the bloom appeared at the sea surface on the 2nd June 2019 and peaked in size and surface abundance in offshore shelf waters within 4 weeks, remnants remained at the surface into July. A particle tracking approach was used to replicate oceanic circulation patterns in the vicinity of the observed algal bloom and estimate its trajectory. The initial horizontal distribution of particles in the tracking model were based on a satellite imagery polygon of the bloom when it first appeared in surface waters. Good agreement was observed between satellite imagery of the bloom and the particle tracking model. In situ sampling efforts from a research cruise and the national inshore phytoplankton monitoring programme confirmed that Karenia mikimotoi was the causative organism of the bloom. This pilot study shows great potential to use the Red Band Difference algorithm in the existing Irish harmful algal bloom alert system. In addition, satellite ocean colour data combined with particle tracking model estimates can be a useful tool to monitor high biomass harmful algal bloom forming species, such as Karenia mikimotoi , in surface coastal waters around Ireland and elsewhere.

Assessing the rockfall protection efficiency of forests at the regional scale - C. Lanfranconi; G. Sala; P. Frattini; G. B. Crosta; A. Valagussa (Landslides, 2020)

Metabolites in cultured cells of Ibervillea sonorae (S. Watson) Greene display increased hypoglycemic activity compared to that seen in plant roots - Ilse-Yazmín Arciniega-Carreón; María-Guadalupe Ramírez-Sotelo; Ana C. Ramos-Valdivia; Carlos Edmundo Salas; Arturo Ortega; Carmen Oliver-Salvador (Horticulture, Environment, and Biotechnology, 2020)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Use of an Argentinean Wildlife Tissue Collection for Epidemiological Studies of Histoplasmosis - Cristina E. Canteros; Adriana I. Toranzo; Silvana Levis; Héctor D. Salas; María C. López-Joffre; Roberto Osvaldo Suárez-Alvarez (Mycopathologia, 2020)

Ecto- and endoparasitic nematodes respond differently across sites to changes in precipitation - Katharine E. Ankrom; André L. C. Franco; Steven J. Fonte; Laureano A. Gherardi; Cecilia Milano de Tomasel; Walter S. Andriuzzi; E. Ashley Shaw; Osvaldo E. Sala; Diana H. Wall (Oecologia, 2020)

Assembly mechanisms and environmental predictors of the phylogenetic diversity of cricetid rodents in southern Mexico - Cintia Natalia Martín-Regalado; Miguel Briones-Salas; Norma Manríquez-Morán; Gerardo Sánchez-Rojas; Cristian Cornejo-Latorre; Mario C. Lavariega; Claudia E. Moreno (Evolutionary Ecology, 2020)

Atmospheric indices allow anticipating the incidence of jellyfish coastal swarms - JUAN J. BELLIDO; JOSÉ C. BÁEZ; LUCRECIA SOUVIRON-PRIEGO; FRANCISCO FERRI-YAÑEZ; CARMEN SALAS; JUAN ANTONIO LÓPEZ; RAIMUNDO REAL (Mediterranean Marine Science, 2020)
Jellyfish swarms affect littoral ecosystems, are unpleasant for bathers and jeopardize coastal socio-economic sectors. Anticipating the incidence of jellyfish swarms could be useful for implementing preventive management measures. Macroclimatic indices are good candidates for this type of anticipation since they are macro-ecologically related to oceanographic characteristics that affect marine species after a certain time lag. An increase of jellyfish swarms has been recently reported in the Mediterranean Sea. From 2005 to 2018, jellyfish swarms in the littoral of the province of Malaga (Spain, northwest coast of the Alboran Sea), mainly formed by the mauve stinger (Pelagia noctiluca), were frequent during summer. We recorded data on jellyfish swarm incidence in the province of Malaga from 2005 to 2018 using the reports in local newspapers, searches in Google Search Engine, and a citizen science application for mobile phones as information sources. With this information, we classified the period in years of low, medium and high incidence of jellyfish swarms. Then, we tested if the known effects of the Arctic Oscillation (AO) and North Atlantic Oscillation (NAO) in winter on the sea surface temperature (SST) during the year, which in turn affects the proliferation of jellyfish, could explain the inter-annual variation in this incidence. Our hypothesis significantly explained the variation in the medium versus low incidence of jellyfish swarms, with medium incidence in the summers of higher SST. This suggests that medium incidence of jellyfish swarms was caused by the proliferation of jellyfish. This also suggests that years of medium incidence of jellyfish in the beach during summer could be anticipated by computing the average AO and NAO values of the previous winter. Years of high incidence of swarms could not be explained by this process. We speculate that they may be caused by a change in the distribution of the swarms rather than by proliferation. Jellyfish may be pushed from the pelagic western anticyclonic gyre of the Alboran Sea to the northern coast by eddies that are formed when, as recent literature has shown, this gyre is weakened by westerly winds and the Atlantic jet. Citizen science has contributed useful data to build macroecological models that may result in better management plans based on scientific data.

Incisor Enamel Microstructure of Paleogene Caviomorph Rodents from Contamana and Shapaja (Peruvian Amazonia) - Myriam Boivin; Laurent Marivaux; Rodolfo Salas-Gismondi; Emma C. Vieytes; Pierre-Olivier Antoine (Journal of Mammalian Evolution, 2019)

Dopamine D2-like receptor stimulation blocks negative feedback in visual and spatial reversal learning in the rat: behavioural and computational evidence - Johan Alsiö; Benjamin U. Phillips; Júlia Sala-Bayo; Simon R. O. Nilsson; Teresa C. Calafat-Pla; Arazo Rizwand; Jessica M. Plumbridge; Laura López-Cruz; Jeffrey W. Dalley; Rudolf N. Cardinal; Adam C. Mar; Trevor W. Robbins (Psychopharmacology, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Long-Term Dynamic in Nutrients, Chlorophyll a, and Water Quality Parameters in a Coastal Lagoon During a Process of Eutrophication for Decades, a Sudden Break and a Relatively Rapid Recovery - Angel Pérez-Ruzafa; Sara Campillo; José María Fernández-Palacios; Antonio García-Lacunza; Miriam García-Oliva; Helena Ibañez; Pedro C. Navarro-Martínez; María Pérez-Marcos; Isabel M. Pérez-Ruzafa; Jhoni Ismael Quispe-Becerra; Antonio Sala-Mirete; Olga Sánchez; et al. (Frontiers in Marine Science, 2019)

Adipocyte proteome and secretome influence inflammatory and hormone pathways in glioma - J. Almeida; J. Costa; P. Coelho; V. Cea; M. Galesio; J. P. Noronha; M. S. Diniz; C. Prudêncio; R. Soares; C. Sala; Rúben Fernandes (Metabolic Brain Disease, 2019)

Parkinson’s disease with mild cognitive impairment: severe cortical thinning antedates dementia - Carmen Gasca-Salas; Daniel García-Lorenzo; David Garcia-Garcia; Pedro Clavero; José A. Obeso; Stephane Lehericy; María C. Rodríguez-Oroz (Brain Imaging and Behavior, 2019)

Management and Succession at the Lick Creek Demonstration/Research Forest, Montana - Justin S Crotteau; Sharon M Hood; Duncan C Lutes; Christopher R Keyes; Anna Sala; Michael G Harrington (Journal of Forestry, 2018)

Limited evidence for CO 2 ‐related growth enhancement in northern Rocky Mountain lodgepole pine populations across climate gradients - Charlotte C. Reed; Ashley P. Ballantyne; Leila Annie Cooper; Anna Sala (Global Change Biology, 2018)
Forests sequester large amounts of carbon annually and are integral in buffering against effects of global change. Increasing atmospheric CO 2 may enhance photosynthesis and/or decrease stomatal conductance (g s ) thereby enhancing intrinsic water‐use efficiency ( iWUE ), having potential indirect and direct benefits to tree growth. While increasing iWUE has been observed in most trees globally, enhanced growth is not ubiquitous, possibly due to concurrent climatic constraints on growth. To investigate our incomplete understanding of interactions between climate and CO 2 and their impacts on tree physiology and growth, we used an environmental gradient approach. We combined dendrochronology with carbon isotope analysis (δ 13 C) to assess the covariation of basal area increment ( BAI ) and iWUE over time in lodgepole pine. Trees were sampled at 18 sites spanning two climatically distinct elevation transects on the lee and windward sides of the Continental Divide, encompassing the majority of lodgepole pine's northern Rocky Mountain elevational range. We analyzed BAI and iWUE from 1950 to 2015, and explored correlations with monthly climate variables. As expected, iWUE increased at all sites. However, concurrent growth trends depended on site climatic water deficit ( CWD ). Significant growth increases occurred only at the driest sites, where increases in iWUE were strongest, while growth decreases were greatest at sites where CWD has been historically lowest. Late summer drought of the previous year negatively affected growth across sites. These results suggest that increasing iWUE , if strong enough, may indirectly benefit growth at drier sites by effectively extending the growing season via reductions in g s . Strong growth decreases at high elevation windward sites may reflect increasing water stress as a result of decreasing snowpack, which was not offset by greater iWUE . Our results imply that increasing iWUE driven by decreasing g s may benefit tree growth in limited scenarios, having implications for future carbon uptake potential of semiarid ecosystems.

Influence of Trichomes in Strawberry Cultivars on the Feeding Behavior of Chaetosiphon fragaefolii (Cockerell) (Hemiptera: Aphididae) - A Benatto; A F Mogor; S C Penteado; L S Pereira; F J S Salas; M A C Zawadneak (Neotropical Entomology, 2018)

Erratum to: Roads to interdisciplinarity – working at the nexus among food systems, nutrition and health - F. Picchioni; E. Aurino; L. Aleksandrowicz; M. Bruce; S. Chesterman; P. Dominguez-Salas; Z. Gersten; S. Kalamatianou; C. Turner; J. Yates (Food Security, 2018)

Polymorphism of the DRD2 Gene in a Mexican Population with Mental Deviations - M. Salas-Magaña; C. A. Tovilla-Zárate; A. Genis; T. B. González-Castro; I. E. Juárez-Rojop; M. L. López-Narvaez (Neurophysiology, 2018)

Age-specific environmental differences on the otolith shape of the bastard grunt (Pomadasys incisus) in the north-western Mediterranean - H. Villegas-Hernández; J. Lloret; M. Muñoz; G. R. Poot-López; S. Guillén-Hernández; C. González-Salas (Environmental Biology of Fishes, 2018)

Regional grassland productivity responses to precipitation during multiyear above‐ and below‐average rainfall periods - Matthew D. Petrie; Debra P. C. Peters; Jin Yao; John M. Blair; Nathan D. Burruss; Scott L. Collins; Justin D. Derner; Laureano A. Gherardi; John R. Hendrickson; Osvaldo E. Sala; Patrick J. Starks; Jean L. Steiner (Global Change Biology, 2018)
There is considerable uncertainty in the magnitude and direction of changes in precipitation associated with climate change, and ecosystem responses are also uncertain. Multiyear periods of above‐ and below‐average rainfall may foretell consequences of changes in rainfall regime. We compiled long‐term aboveground net primary productivity ( ANPP ) and precipitation ( PPT ) data for eight North American grasslands, and quantified relationships between ANPP and PPT at each site, and in 1–3 year periods of above‐ and below‐average rainfall for mesic, semiarid cool, and semiarid warm grassland types. Our objective was to improve understanding of ANPP dynamics associated with changing climatic conditions by contrasting PPT – ANPP relationships in above‐ and below‐average PPT years to those that occurred during sequences of multiple above‐ and below‐average years. We found differences in PPT – ANPP relationships in above‐ and below‐average years compared to long‐term site averages, and variation in ANPP not explained by PPT totals that likely are attributed to legacy effects. The correlation between ANPP and current‐ and prior‐year conditions changed from year to year throughout multiyear periods, with some legacy effects declining, and new responses emerging. Thus, ANPP in a given year was influenced by sequences of conditions that varied across grassland types and climates. Most importantly, the influence of prior‐year ANPP often increased with the length of multiyear periods, whereas the influence of the amount of current‐year PPT declined. Although the mechanisms by which a directional change in the frequency of above‐ and below‐average years imposes a persistent change in grassland ANPP require further investigation, our results emphasize the importance of legacy effects on productivity for sequences of above‐ vs. below‐average years, and illustrate the utility of long‐term data to examine these patterns.

A Simple Method for the Purification of Nisin - Ronan Gough; Beatriz Gómez-Sala; Paula M. O’Connor; Mary C. Rea; Song Miao; Colin Hill; André Brodkorb (Probiotics and Antimicrobial Proteins, 2017)

Clinical significance and outcome of Aeromonas spp. infections among 204 adult patients - J. Nolla-Salas; J. Codina-Calero; S. Vallés-Angulo; A. Sitges-Serra; A. Zapatero-Ferrándiz; M. C. Climent; J. Gómez; J. R. Masclans (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Effects of dietary Gracilaria sp. and Alaria sp. supplementation on growth performance, metabolic rates and health in meagre (Argyrosomus regius) subjected to pathogen infection - Maria João Peixoto; Emílio Salas-Leitón; Francisca Brito; Luís Ferreira Pereira; Jon C. Svendsen; Teresa Baptista; Rui Pereira; Helena Abreu; Pedro Alexandre Reis; José Fernando Magalhães Gonçalves; Rodrigo Otávio de Almeida Ozório (Journal of Applied Phycology, 2017)

Roads to interdisciplinarity – working at the nexus among food systems, nutrition and health - F. Picchioni; E. Aurino; L. Aleksandrowicz; M. Bruce; S. Chesterman; P. Dominguez-Salas; Z. Gersten; S. Kalamatianou; C. Turner; J. Yates (Food Security, 2017)

Probiotic Lactobacillus fermentum UCO-979C biofilm formation on AGS and Caco-2 cells and Helicobacter pylori inhibition - M. J. Salas-Jara; E. A. Sanhueza; A. Retamal-Díaz; C. González; H. Urrutia; A. García (Biofouling, 2016)

Erratum to: Identifying landslide preconditions in Swedish quick clays—insights from integration of surface geophysical, core sample- and downhole property measurements - Silvia Salas-Romero; Alireza Malehmir; Ian Snowball; Bryan C. Lougheed; Magnus Hellqvist (Landslides, 2016)

Identifying landslide preconditions in Swedish quick clays—insights from integration of surface geophysical, core sample- and downhole property measurements - Silvia Salas-Romero; Alireza Malehmir; Ian Snowball; Bryan C. Lougheed; Magnus Hellqvist (Landslides, 2016)

Is it possible to prevent recurrent vulvovaginitis? The role of Lactobacillus plantarum I1001 (CECT7504) - S. Palacios; J. Espadaler; J. M. Fernández-Moya; C. Prieto; N. Salas (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Seasonality and trophic diversity in molluscan assemblages from the Bay of Tunis (southern Mediterranean Sea) - M. ANTIT; A. DAOULATLI; J. URRA; J. L. RUEDA; S. GOFAS; C. SALAS (Mediterranean Marine Science, 2016)
Soft bottom molluscan assemblages from the Bay of Tunis have been studied in order to analyse their seasonality and trophic diversity in relation to environmental variables. A total of 147 species of molluscs was identified, with gastropods displaying the highest species richness and bivalves the highest abundances, and including five non-indigenous species such as the dominant ectoparasite Polycerella emertoni. Carnivorous and scavenger gastropods were among the most frequent species, reflecting a diverse benthic community. Seasonal changes were significant, being more acute at 3-4 m than at 10-15 m depth, and were driven mainly by seawater temperature and percentage of organic matter in the sediment. The high affluence of tourists in summer was coincident with high decreases in species richness and abundance of molluscs, together with a strong siltation of the sediment. Nevertheless, most trophic groups remained and the trophic diversity was relatively high. Significant relationships were found between the index of trophic diversity and Shannon-Wiener diversity and evenness indices, suggesting that the identity of the species with its particular trophic trait, together with the good distribution of the individuals among the species (density) would be the drivers for the maintenance of the molluscan food web under environmental stress. The abundance of P. emertoni altered the trophic structure of the molluscan assemblage, with the ectoparasite trophic group reaching an unusual punctual higher dominance. Soft bottom molluscan assemblages of the Bay of Tunis should be taken into account in monitoring programs for anthropogenic impacts and non-indigenous species trends throughout the Mediterranean basin.

Adherence to Mediterranean diet is associated with methylation changes in inflammation-related genes in peripheral blood cells - A. Arpón; J. I. Riezu-Boj; F. I. Milagro; A Marti; C. Razquin; M. A. Martínez-González; D. Corella; R. Estruch; R. Casas; M. Fitó; E. Ros; J. Salas-Salvadó; et al. (Journal of Physiology and Biochemistry, 2016)

Challenges and emerging technical solutions in on-growing salmon farming - O. I. Lekang; C. Salas-Bringas; J. C. Bostock (Aquaculture International, 2016)

Complex Population Patterns of Eunica tatila Herrich-Schäffer (Lepidoptera: Nymphalidae), with Special Emphasis on Sexual Dimorphism - L Cavanzón-Medrano; C Pozo; Y Hénaut; L Legal; N Salas-Suárez; S Machkour-M’Rabet (Neotropical Entomology, 2016)

Determinants of the t(14;18) translocation and their role in t(14;18)-positive follicular lymphoma - Rachel S. Kelly; Sandrine Roulland; Ester Morgado; Stéphanie Sungalee; Nathalie Jouve; Rosario Tumino; Vittorio Krogh; Salvatore Panico; Silvia Polidoro; Giovanna Masala; María-José Sánchez; Maria-Dolores Chirlaque; et al. (Cancer Causes & Control, 2015)

Arsenic levels in immigrant children from countries at risk of consuming arsenic polluted water compared to children from Barcelona - S. Piñol; A. Sala; C. Guzman; S. Marcos; X. Joya; C. Puig; M. Velasco; D. Velez; O. Vall; O. Garcia-Algar (Environmental Monitoring and Assessment, 2015)

Fate and source distribution of organic constituents in a river-dominated tropical estuary - P M SALAS; C H SUJATHA; C S RATHEESH KUMAR (Journal of Earth System Science, 2015)

Enhanced precipitation variability effects on water losses and ecosystem functioning: differential response of arid and mesic regions - Osvaldo E. Sala; Laureano A. Gherardi; Debra P. C. Peters (Climatic Change, 2015)

Comment on “Evidence from acoustic imaging for submarine volcanic activity in 2012 off the west coast of El Hierro (Canary Islands, Spain)” by Pérez NM, Somoza L, Hernández PA, González de Vallejo L, León R, Sagiya T, Biain A, González FJ, Medialdea T, Barrancos J, Ibáñez J, Sumino H, Nogami K and Romero C [Bull Volcanol (2014) 76:882-896] - M. J. Blanco; E. Fraile-Nuez; A. Felpeto; J. M. Santana-Casiano; R. Abella; L. M. Fernández-Salas; J. Almendros; V. Díaz-del-Río; I. Domínguez Cerdeña; L. García-Cañada; M. González-Dávila; C. López; et al. (Bulletin of Volcanology, 2015)

An assessment of a multi-model ensemble of decadal climate predictions - A. Bellucci; R. Haarsma; S. Gualdi; P. J. Athanasiadis; M. Caian; C. Cassou; E. Fernandez; A. Germe; J. Jungclaus; J. Kröger; D. Matei; W. Müller; et al. (Climate Dynamics, 2015)

Soil animal responses to moisture availability are largely scale, not ecosystem dependent: insight from a cross‐site study - Zachary A. Sylvain; Diana H. Wall; Karie L. Cherwin; Debra P. C. Peters; Lara G. Reichmann; Osvaldo E. Sala (Global Change Biology, 2014)
Climate change will result in reduced soil water availability in much of the world either due to changes in precipitation or increased temperature and evapotranspiration. How communities of mites and nematodes may respond to changes in moisture availability is not well known, yet these organisms play important roles in decomposition and nutrient cycling processes. We determined how communities of these organisms respond to changes in moisture availability and whether common patterns occur along fine‐scale gradients of soil moisture within four individual ecosystem types (mesic, xeric and arid grasslands and a polar desert) located in the western United States and Antarctica, as well as across a cross‐ecosystem moisture gradient ( CEMG ) of all four ecosystems considered together. An elevation transect of three sampling plots was monitored within each ecosystem and soil samples were collected from these plots and from existing experimental precipitation manipulations within each ecosystem once in fall of 2009 and three times each in 2010 and 2011. Mites and nematodes were sorted to trophic groups and analyzed to determine community responses to changes in soil moisture availability. We found that while both mites and nematodes increased with available soil moisture across the CEMG , within individual ecosystems, increases in soil moisture resulted in decreases to nematode communities at all but the arid grassland ecosystem; mites showed no responses at any ecosystem. In addition, we found changes in proportional abundances of mite and nematode trophic groups as soil moisture increased within individual ecosystems, which may result in shifts within soil food webs with important consequences for ecosystem functioning. We suggest that communities of soil animals at local scales may respond predictably to changes in moisture availability regardless of ecosystem type but that additional factors, such as climate variability, vegetation composition, and soil properties may influence this relationship over larger scales.

Hydrology of the Jordan River Basin: A GIS-Based System to Better Guide Water Resources Management and Decision Making - Georges F. Comair; Daene C. McKinney; David R. Maidment; Gonzalo Espinoza; Harish Sangiredy; Abbas Fayad; Fernando R. Salas (Water Resources Management, 2014)

Subtle genetic connectivity between Mexican Caribbean and south-western Gulf of Mexico reefs: the case of the bicolor damselfish, Stegastes partitus - C. A. Villegas Sánchez; H. Pérez España; R. Rivera Madrid; D. Salas Monreal; J. E. Arias González (Coral Reefs, 2014)

Erratum to: Regional hydrological cycle changes in response to an ambitious mitigation scenario - H. Huebener; M. G. Sanderson; I. Höschel; J. Körper; T. C. Johns; J.-F. Royer; E. Roeckner; E. Manzini; J.-L. Dufresne; O. H. Otterå; J. Tjiputra; D. Salas y Melia; et al. (Climatic Change, 2013)

Regional hydrological cycle changes in response to an ambitious mitigation scenario - H. Huebener; M. G. Sanderson; I. Höschel; J. Körper; T. C. Johns; J.-F. Royer; E. Roeckner; E. Manzini; J.-L. Dufresne; O. H. Otterå; J. Tjiputra; D. Salas y Melia; et al. (Climatic Change, 2013)

Temporal variation of the algae-associated molluscan assemblage of artificial substrata in Bay of Tunis (Tunisia) - M. ANTIT; A. DAOULATLI; J.L. RUEDA; C. SALAS (Mediterranean Marine Science, 2013)
The molluscan assemblage inhabiting the photophilous algae from artificial rocky shores in theBay of Tunis) was studied from February 2009 to February 2010. Five monthly replicates were taken with a quadrat of 25 × 25 cm .. A total of 16105 individuals of molluscs, belonging to 93 species, were collected. Gastropods were the most species-rich group, with 66 species (70.96%), followed by bivalves with 26 species (27.95%). Gastropods were also the most abundant with 11529 individuals (71.60%), followed by bivalves with 4575 individuals (28.41%). Nevertheless,Mytilaster minimus was the dominant species overall during the studied period (15.6% of total abundance), followed by Tricolia miniata (11.6%), Bittium reticulatum (11.5%), Gibbula racketti (10.4%) and Rissoa similis (9.8%). The high abundance of juveniles of soft (e.g. Venerupis aurea, Nassarius corniculum) and hard bottom species (e.g. M. minimus, Fissurella nubecula) point out the important role of this habitat as nursery for species from nearby located habitats. The presence of the alien molluscs Mitrella psilla (2.5% dominance) and Arcuatula senhousia highlights the importance of algae as vehicle and/or receptor habitat for alien species. Species richness and abundance displayed significant seasonal changes, with maxima in winter 2009, but the Shannon-Wiener diversity index showed similar values throughout the year. Multivariate analyses also indicated the presence of significant seasonal differences of this molluscan assemblage.

Skill assessment of three earth system models with common marine biogeochemistry - Roland Séférian; Laurent Bopp; Marion Gehlen; James C. Orr; Christian Ethé; Patricia Cadule; Olivier Aumont; David Salas y Mélia; Aurore Voldoire; Gurvan Madec (Climate Dynamics, 2013)

The CNRM-CM5.1 global climate model: description and basic evaluation - A. Voldoire; E. Sanchez-Gomez; D. Salas y Mélia; B. Decharme; C. Cassou; S. Sénési; S. Valcke; I. Beau; A. Alias; M. Chevallier; M. Déqué; J. Deshayes; et al. (Climate Dynamics, 2013)

Undernutrition upregulates fumarate hydratase in the rat nucleus accumbens - E. Lizárraga-Mollinedo; C. Álvarez; E. Fernández-Millán; F. Escrivá; C. González-Martín; E. Salas; J. M. Pérez-Ortiz; L. F. Alguacil (Metabolic Brain Disease, 2013)

The effects of aggressive mitigation on steric sea level rise and sea ice changes - J. Körper; I. Höschel; J. A. Lowe; C. D. Hewitt; D. Salas y Melia; E. Roeckner; H. Huebener; J.-F. Royer; J.-L. Dufresne; A. Pardaens; M. A. Giorgetta; M. G. Sanderson; et al. (Climate Dynamics, 2013)

New eastern Pacific Ocean records of Hydrolagus melanophasma , with annotations of a juvenile female - H. Aguirre‐Villaseñor; C. Salas‐Singh; J. Madrid‐Vera; J. Martínez‐Ortiz; D. A. Didier; D. A. Ebert (Journal of Fish Biology, 2013)
Two new records of Hydrolagus melanophasma , one juvenile female from off the central Mexican coast and one adult male from off the coast of Ecuador, confirm the presence of this species throughout its known range in the eastern Pacific Ocean, from southern California, U.S.A., to Valdivia, Chile. This report gives a description and comparison of proportional measurements, head shape and colouration for juvenile and adult H. melanophasma . A taxonomic key to distinguish the eastern Pacific Ocean species of Hydrolagus is included.

Precipitation legacies in desert grassland primary production occur through previous‐year tiller density - Lara G. Reichmann; Osvaldo E. Sala; Debra P. C. Peters (Ecology, 2013)
In arid ecosystems, current‐year precipitation often explains only a small proportion of annual aboveground net primary production (ANPP). We hypothesized that lags in the response of ecosystems to changes in water availability explain this low explanatory power, and that lags result from legacies from transitions from dry to wet years or the reverse. We explored five hypotheses regarding the magnitude of legacies, two possible mechanisms, and the differential effect of previous dry or wet years on the legacy magnitude. We used a three‐year manipulative experiment with five levels of rainfall in the first two years (−80% and −50% reduced annual precipitation (PPT), ambient, +50% and +80% increased PPT), and reversed treatments in year 3. Legacies of previous two years, which were dry or wet, accounted for a large fraction (20%) of interannual variability in production on year 3. Legacies in ANPP were similar in absolute value for both types of precipitation transitions, and their magnitude was a function of the difference between previous and current‐year precipitation. Tiller density accounted for 40% of legacy variability, while nitrogen and carry‐over water availability showed no effect. Understanding responses to changes in interannual precipitation will assist in assessing ecosystem responses to climate change‐induced increases in precipitation variability.

Alien species in the Mediterranean Sea by 2012. A contribution to the application of European Union’s Marine Strategy Framework Directive (MSFD). Part 2. Introduction trends and pathways - Α. ZENETOS; S. GOFAS; C. MORRI; A. ROSSO; D. VIOLANTI; J.E. GARCIA RASO; M.E. CINAR; A. ALMOGI-LABIN; A.S. ATES; E. AZZURRO; E. BALLESTEROS; C.N. BIANCHI; et al. (Mediterranean Marine Science, 2012)
More than 60 marine non-indigenous species (NIS) have been removed from previous lists and 84 species have been added, bringing the total to 986 alien species in the Mediterranean [775 in the eastern Mediterranean (EMED), 249 in the central Mediterranean (CMED), 190 in the Adriatic Sea (ADRIA) and 308 in the western Mediterranean (WMED)]. There were 48 new entries since 2011 which can be interpreted as approximately one new entry every two weeks. The number of alien species continues to increase, by 2-3 species per year for macrophytes, molluscs and polychaetes, 3-4 species per year for crustaceans, and 6 species per year for fish. The dominant group among alien species is molluscs (with 215 species), followed by crustaceans (159) and polychaetes (132). Macrophytes are the leading group of NIS in the ADRIA and the WMED, reaching 26-30% of all aliens, whereas in the EMED they barely constitute 10% of the introductions. In the EMED, molluscs are the most species-rich group, followed by crustaceans, fish and polychaetes. More than half (54%) of the marine alien species in the Mediterranean were probably introduced by corridors (mainly Suez). Shipping is blamed directly for the introduction of only 12 species, whereas it is assumed to be the most likely pathway of introduction (via ballasts or fouling) of another 300 species. For approximately 100 species shipping is a probable pathway along with the Suez Canal and/or aquaculture. Approximately 20 species have been introduced with certainty via aquaculture, while >50 species (mostly macroalgae), occurring in the vicinity of oyster farms, are assumed to be introduced accidentally as contaminants of imported species. A total of 18 species are assumed to have been introduced by the aquarium trade. Lessepsian species decline westwards, while the reverse pattern is evident for ship-mediated species and for those introduced with aquaculture. There is an increasing trend in new introductions via the Suez Canal and via shipping.

Development of a Multiplex PCR Assay to Detect Gastroenteric Pathogens in the Feces of Mexican Children - R. Tolentino-Ruiz; D. Montoya-Varela; M. García-Espitia; M. Salas-Benito; A. Gutiérrez-Escolano; C. Gómez-García; P. Figueroa-Arredondo; J. Salas-Benito; M. De Nova-Ocampo (Current Microbiology, 2012)

Quantitative trait loci associated with grain moisture at harvest for line per se and testcross performance in maize: a meta-analysis - Rodrigo G. Sala; Fernando H. Andrade; Julio C. Cerono (Euphytica, 2012)

High prevalence of upper urinary tract involvement detected by 111indium-oxine leukocyte scintigraphy in patients with candiduria - J. P. Horcajada; M. Gutiérrez-Cuadra; I. Martínez-Rodríguez; C. Salas; J. A. Parra; N. Benito; R. Quirce; J. M. Carril; M. C. Fariñas (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Directional climate change and potential reversal of desertification in arid and semiarid ecosystems - Debra P. C. Peters; Jin Yao; Osvaldo E. Sala; John P. Anderson (Global Change Biology, 2012)
Our objective was to determine if long‐term increases in precipitation can maintain grasslands susceptible to desertification, and initiate a reversal of historic regime shifts on desertified shrublands. Perennial grass production and species richness in a multi‐year wet period were hypothesized to be greater than expected based on precipitation in a sequence of dry years. These responses were expected to differ for grasslands and shrublands with different dominant species and topo‐edaphic properties. Long‐term trends in desertification were documented using vegetation maps beginning in 1858, 1915, 1928, and 1998). These trends were compared with herbaceous and woody species responses to a sequence of dry (1994–2003) and wet years (2004–2008) for two grassland (uplands, playas) and three desertified shrubland types (honey mesquite, creosotebush, tarbush) in the Chihuahuan Desert. Analyses showed that both types of grasslands decreased in spatial extent since 1858 whereas areas dominated by mesquite or creosotebush increased. Production of upland grasslands in the wet period was greater than expected based on responses during the dry period whereas the relationships between species richness and precipitation was the same for both periods. Precipitation was not important to responses in playa grasslands in either period. For all ecosystem types, the production response in wet years primarily was an increase in herbaceous plants, and the most pronounced responses occurred on sandy sites (upland grasslands, mesquite shrubland). Results suggest that multiple wet years are needed to initiate a sequence of grass establishment and survival processes that can maintain upland grasslands without management inputs and lead to a state change reversal in desertified shrublands. Restoration strategies need to take advantage of opportunities provided by future climates while recognizing the importance of ecosystem type.

Climate change under aggressive mitigation: the ENSEMBLES multi-model experiment - T. C. Johns; J.-F. Royer; I. Höschel; H. Huebener; E. Roeckner; E. Manzini; W. May; J.-L. Dufresne; O. H. Otterå; D. P. van Vuuren; D. Salas y Melia; M. A. Giorgetta; et al. (Climate Dynamics, 2011)

Update on the Relationship of Fish Intake with Prostate, Breast, and Colorectal Cancers - Aleix Sala-Vila; Philip C. Calder (Critical Reviews in Food Science and Nutrition, 2011)

Erratum to: Climate change under aggressive mitigation: the ENSEMBLES multi-model experiment - T. C. Johns; J.-F. Royer; I. Höschel; H. Huebener; E. Roeckner; E. Manzini; W. May; J.-L. Dufresne; O. H. Otterå; D. P. van Vuuren; D. Salas y Melia; M. A. Giorgetta; et al. (Climate Dynamics, 2011)

Laticifer proteins play a defensive role against hemibiotrophic and necrotrophic phytopathogens - Diego P. Souza; Cleverson D. T. Freitas; Danielle A. Pereira; Fábio C. Nogueira; Fredy D. A. Silva; Carlos E. Salas; Márcio V. Ramos (Planta, 2011)

ON‐FARM EVALUATION OF FERTILIZER BRIQUETTES AND LOW‐COST DRIP IRRIGATION FOR SMALLHOLDER VEGETABLE PRODUCTION IN CAMBODIA - S. P. Bhattarai; M. C. Palada; D. J. Midmore; D. Wu; R. Salas (Irrigation and Drainage, 2011)
The performance of low cost drip irrigation (LCDI) compared to hand watering (HW), as well as NPK fertilizer briquette deep placement (FBDP) compared to conventional compound fertilizer (CCF), for vegetable production was evaluated. Yield and water use efficiency (WUE) increased significantly with LCDI compared to HW on cucumber (13 and 41%), sponge gourd (85 and 129%), eggplant (38 and 113%), bitter gourd (121 and 35%) and long bean (5 and 27%) respectively. Yield and WUE of cucumber (22 and 25%) and long bean (9% and 12%) increased with FBDP compared to CCF. Net income due to FBDP was greater by 24 and 14% for cucumber and long bean, respectively, compared to CCF. The number of man‐days employed for irrigation increased six times in HW compared to LCDI. Net return with LCDI was greater by 52% compared to HW and varied from 4 to 121% between the crops. Combined over two trials, yield and WUE increased by 37% (5.589 vs 4.065 Mg ha −1 ) and 123% (4.28 vs 1.916 Mg ML −1 ) respectively, with less applied water in LCDI compared to HW (1.687 vs 2.78 ML ha −1 ). LCDI and FBDP can significantly improve yield, WUE and profitability of the small‐scale vegetable growers in Cambodia. Copyright © 2010 John Wiley & Sons, Ltd.

One hundred years after Pinctada: an update on alien Mollusca in Tunisia - M. ANTIT; S. GOFAS; C. SALAS; A. AZZOUNA (Mediterranean Marine Science, 2011)
The occurrences of non-indigenous marine molluscs in Tunisia are reviewed, based booth on a literature survey and on original material. Species are accepted as established if there are two independent reports, either geographically separate or at least one month apart in time. On these grounds, 14 species are accepted (12 alien and 2 expanding their range from elsewhere in the Mediterranean), 3 aliens need confirmation but are likely to meet the standards for acceptation on a short future, and 5 records are rebutted or questioned. Two more species may be considered as cryptogenic, the reports are reliable but it is not clear indication that they are not indigenous. Two of the alien species are reported for the first time in Tunisian waters: the nudibranch Polycerella emertoni qualifies as established, and the bivalve Anadara transversa is tentatively identified from a juvenile live-taken specimen, which awaits further confirmation.The occurrence of aliens in Tunisia is balanced between presumably Lessepsian species of tropical Indo-Pacific origin, and species from other sources including species from the Tropical Atlantic introduced through shipping. Nevertheless there is a prevalence of Lessepsian species towards the Gulf of Gabes in the south, whereas the shipping activity in Tunis harbour may be the main pathway of introduction in the north.

Natural forcing of climate during the last millennium: fingerprint of solar variability - D. Swingedouw; L. Terray; C. Cassou; A. Voldoire; D. Salas-Mélia; J. Servonnat (Climate Dynamics, 2011)

Robust QCT/FEA Models of Proximal Femur Stiffness and Fracture Load During a Sideways Fall on the Hip - Dan Dragomir-Daescu; Jorn Op Den Buijs; Sean McEligot; Yifei Dai; Rachel C. Entwistle; Christina Salas; L. Joseph Melton; Kevin E. Bennet; Sundeep Khosla; Shreyasee Amin (Annals of Biomedical Engineering, 2011)

A novel subaerial Dunaliella species growing on cave spiderwebs in the Atacama Desert - A. Azúa-Bustos; C. González-Silva; L. Salas; R. E. Palma; R. Vicuña (Extremophiles, 2010)

Collection and characterization of yellow endosperm sorghums from West Africa for biofortification - M. G. Salas Fernandez; I. Kapran; S. Souley; M. Abdou; I. H. Maiga; C. B. Acharya; M. T. Hamblin; S. Kresovich (Genetic Resources and Crop Evolution, 2009)

Sheep Grazing Decreases Organic Carbon and Nitrogen Pools in the Patagonian Steppe: Combination of Direct and Indirect Effects - Rodolfo A. Golluscio; Amy T. Austin; Guillermo C. García Martínez; Marina Gonzalez-Polo; Osvaldo E. Sala; Robert B. Jackson (Ecosystems, 2009)

The Depressive Phenotype Induced in Adult Female Rats by Adolescent Exposure to THC is Associated with Cognitive Impairment and Altered Neuroplasticity in the Prefrontal Cortex - T. Rubino; N. Realini; D. Braida; T. Alberio; V. Capurro; D. Viganò; C. Guidali; M. Sala; M. Fasano; D. Parolaro (Neurotoxicity Research, 2009)

The Late Pleistocene clastic deposits in the Romito Cave, southern Italy: a proxy record of environmental changes and human presence - Massimiliano Ghinassi; Andrè C. Colonese; Zelia Di Giuseppe; Lisa Govoni; Domenico Lo Vetro; Giulia Malavasi; Fabio Martini; Silvia Ricciardi; Benedetto Sala (Journal of Quaternary Science, 2009)
Clastic sediments deposited in caves and rock shelters bear peculiar sedimentological characteristics and have seldom been considered as a high‐resolution proxy record of climatic or environmental changes. The Romito Cave has its entrance at 275 m above sea level, about 25 km from the Tyrrhenian coast of Calabria, southern Italy. New archaeological excavation performed since 2000 has revealed a sedimentary succession spanning the record of Gravettian to Late Epigravettian cultures (Late Pleistocene). The present study focuses on the lower part (2.5 m thick) of the succession, where three main unconformity‐bounded stratigraphic units have been recognised (labelled RM1–3). Each unit consists of water‐lain deposits indicating high‐ to low‐competence flow, capped with anthropogenic deposits. The gradual deactivation and reactivation of the water drainage between 23 475 ± 190 and 16 250 ± 500 cal. a BP is correlated with regional precipitation changes due to the onset of dry climatic conditions of the Last Glacial Maximum. However, the deactivation of cave drainage after the deposition of unit RM3, around 15 400 ± 500 cal. a BP, deviates from the regional hydrological trend of progressively increasing water discharges and is attributed to the drainage cut‐off by probable cave wall collapses. Copyright © 2008 John Wiley & Sons, Ltd.

Sheep management and cryptosporidiosis in central Mexico - M. U. Alonso-Fresán; J. C. Vázquez-Chagoyán; V. Velázquez-Ordoñez; N. Pescador-Salas; J. Saltijeral-Oaxaca (Tropical Animal Health and Production, 2009)

Early detection of oxidized surfaces using Shewanella oneidensis MR-1 as a tool - M. S. Waters; E. C. Salas; S. D. Goodman; F. E. Udwadia; K. H. Nealson (Biofouling, 2009)

A community outbreak of Legionnaires’ disease associated with a cooling tower in Vic and Gurb, Catalonia (Spain) in 2005 - M. R. Sala Ferré; C. Arias; J. M. Oliva; A. Pedrol; M. García; T. Pellicer; P. Roura; A. Domínguez (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Vitamin C transporters - C. I. Rivas; F. A. Zúñiga; A. Salas-Burgos; L. Mardones; V. Ormazabal; J. C. Vera (Journal of Physiology and Biochemistry, 2008)

Floral nectar chemical composition of floral nectar in conventional and transgenic sweet orange, Citrus sinensis (L.) Osbeck, expressing an antibacterial peptide - V. Sala Junior; V. R. Celloto; L. G. E. Vieira; J. E. Gonçalves; R. A. C. Gonçalves; A. J. B. de Oliveira (Plant Systematics and Evolution, 2008)

Climate continentality and treeline species distribution in the Alps - M. Caccianiga; C. Andreis; S. Armiraglio; G. Leonelli; M. Pelfini; D. Sala (Plant Biosystems, 2008)

Monitoring of coastal and transitional waters under the E.U. Water Framework Directive - J. G. Ferreira; C. Vale; C. V. Soares; F. Salas; P. E. Stacey; S. B. Bricker; M. C. Silva; J. C. Marques (Environmental Monitoring and Assessment, 2007)

Applicability of ecological evaluation tools in estuarine ecosystems: the case of the lower Mondego estuary (Portugal) - H. Teixeira; F. Salas; M. A. Pardal; J. C. Marques (Hydrobiologia, 2007)

Written Accounts of an Amazonian Landscape Over the Last 450 Years - NIGEL C. A. PITMAN; MARÍA DEL CARMEN LOYOLA AZÁLDEGUI; KARINA SALAS; GABRIELA T. VIGO; DAVID A. LUTZ (Conservation Biology, 2007)
Books, articles, government documents, and other written accounts of tropical biology and conservation reach a tiny fraction of their potential audience. Some texts are inaccessible because of the language in which they are written. Others are only available to subscribers of developed‐world journals, or distributed narrowly within tropical countries. To examine this dysfunction in the tropical literature—and what it means for conservation—we tried to compile everything ever written on the biology and conservation of the department of Madre de Dios, Peru, in southwestern Amazonia. Our search of libraries, databases, and existing bibliographies uncovered 2,202 texts totaling roughly 80,000 pages. Texts date from 1553 to 2004, but 93% were written after 1970. Since that year the publication rate has increased steadily from fewer than 10 texts/year to nearly 3 texts/week in 2004. Roughly half of the Madre de Dios bibliography is in Spanish‐language texts written by Peruvian authors and mostly inaccessible outside Peru. Most of the remaining material is English‐language texts written by foreign authors and largely inaccessible in Peru. Foreign authors tended to write about ecological studies with limited relevance to on‐the‐ground conservation challenges, whereas Peruvian authors were more likely to make specific management recommendations. The establishment of a Web‐based digital library for Neotropical nature would help make the tropical literature a more efficient resource for science and conservation. Additional recommendations include investing in syntheses, translations, popular summaries, and peer‐reviewed journals in tropical countries, providing incentives for management‐relevant research in tropical protected areas, and reinforcing training of scientific reading and writing in tropical universities.

Interannual variability and intraannual stability of the otolith shape in European anchovy Engraulis encrasicolus (L.) in the Bay of Biscay - C. Gonzalez‐Salas; P. Lenfant (Journal of Fish Biology, 2007)
In this study 1047 samples of European anchovy Engraulis encrasicolus caught in 2001, 2002 and 2003 in different areas of the Bay of Biscay were examined using otolith shape analysis. For the years 2001 and 2003, 1 year‐old individuals were dominant, whereas for the year 2002 they were less common; in contrast 2 year‐old individuals represented 74% of the total individuals, suggesting that the fisheries in 2002 were mainly supported by the strong recruitment of 2000. The classification success of the discriminant analysis indicated a strong separation between year groups ( P

Genetic mapping of seed shape in three populations of recombinant inbred lines of soybean (Glycine max L. Merr.) - P. Salas; J. C. Oyarzo-Llaipen; D. Wang; K. Chase; L. Mansur (Theoretical and Applied Genetics, 2006)

Reconciling Carbon-cycle Concepts, Terminology, and Methods - F. S. Chapin; G. M. Woodwell; J. T. Randerson; E. B. Rastetter; G. M. Lovett; D. D. Baldocchi; D. A. Clark; M. E. Harmon; D. S. Schimel; R. Valentini; C. Wirth; J. D. Aber; et al. (Ecosystems, 2006)

Structure of Caribbean coral reef communities across a large gradient of fish biomass - Marah J. H. Newman; Gustavo A. Paredes; Enric Sala; Jeremy B. C. Jackson (Ecology Letters, 2006)
The collapse of Caribbean coral reefs has been attributed in part to historic overfishing, but whether fish assemblages can recover and how such recovery might affect the benthic reef community has not been tested across appropriate scales. We surveyed the biomass of reef communities across a range in fish abundance from 14 to 593 g m −2 , a gradient exceeding that of any previously reported for coral reefs. Increased fish biomass was correlated with an increased proportion of apex predators, which were abundant only inside large marine reserves. Increased herbivorous fish biomass was correlated with a decrease in fleshy algal biomass but corals have not yet recovered.

Distinction between Mulloidichthys flavolineatus juveniles from Reunion Island and Mauritius Island (south‐west Indian Ocean) based on otolith morphometrics - K. Pothin; C. Gonzalez‐Salas; P. Chabanet; R. Lecomte‐Finiger (Journal of Fish Biology, 2006)
Sagittal otoliths of the yellowstripe goatfish Mulloidichthys flavolineatus were analysed in order to compare Reunion Island fish stocks with those of Mauritius (south‐west Indian Ocean). Conventional otolith morphometric variables (area, perimeter, length and width), shape indices (form factor, roundness, circularity, rectangularity, ellipticity and eccentricity) and Fourier shape analysis were compared between three sites; two in Reunion Island and one in Mauritius. Regional and site‐specific differences were found for all the conventional otolith morphometric features. Regarding the shape indices, the differences between sites were best described by form factor, roundness, circularity and rectangularity. A classification by canonical discriminant analysis indicated significant differences between the three sampling sites. The combined use of morphometric variables (size and shape) and external outlines (shape analysis through Fourier series) showed the importance of otolith shape for intraspecific discrimination.

Removing Uranium and Radium from a Natural Water - A. Baeza; M. Fernández; M. Herranz; F. Legarda; C. Miró; A. Salas (Water, Air, & Soil Pollution, 2006)

From “Snakebites in the new millennium: A state-of-the-art symposium” - J. Audi; S. A. Seifert; J. F. Gennaro; J. W. Skimming; L. H. S. Van Mierop; C. S. Kitchens; M. D. Cardwell; S. P. Bush; R. T. Clark; E. A. Dugan; R. C. Dart; S. R. Rose; et al. (Journal of Medical Toxicology, 2006)

Quantitative trait loci for grain moisture at harvest and field grain drying rate in maize (Zea mays, L.) - Rodrigo G. Sala; Fernando H. Andrade; Elsa L. Camadro; Julio C. Cerono (Theoretical and Applied Genetics, 2006)

Growth of organ systems of Dentex dentex (L) and Psetta maxima (L) during larval development - R. Sala; C. A. Santamaría; S. Crespo (Journal of Fish Biology, 2005)
Growth in volume of common dentex Dentex dentex and turbot Psetta maxima during larval development was studied by means of a quantitative histological method. A two‐phase pattern of volume increase was recorded for both species, turbot volume being always higher than dentex volume. During the first phase, the increase was small but during the second phase volume rose sharply from 22 days post hatch (dph) and 17 dph onwards in dentex and turbot, respectively. In dentex, the specific growth rate ( G ) of the whole larva as well as that of all the structures studied (nervous tissue, trunk musculature, digestive tract, liver, pancreas, spleen and thymus) was always higher during the second phase, whereas in turbot, only total volume of the larva, trunk musculature and nervous tissue had a higher G during the same period. The pattern of allometric growth of digestive organs was similar for both species. These organs showed an initial positive allometric growth that later became near‐isometric (digestive tract and liver) or negative (pancreas). In dentex, nervous tissue and trunk musculature showed near‐isometry throughout the period studied. In turbot, nervous tissue exhibited negative allometry and trunk musculature changed from negative to positive allometry. In both species studied, the highest allometry coefficients were recorded for digestive organs before the larva switched to strict exotrophy. This would indicate the importance of the development of these organs for survival.

Genomic stability in Arabidopsis thaliana transgenic plants obtained by floral dip - M. Labra; C. Vannini; F. Grassi; M. Bracale; M. Balsemin; B. Basso; F. Sala (Theoretical and Applied Genetics, 2004)

Pneumococcal bacteremia in children: an 8-year review in two hospitals in Barcelona - A. Prez; P. Sala; M. Gimnez; M. Sierra; A. Esteve; A. Alonso; M. Quesada; F. Raspall; V. Ausina; C. Rodrigo (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

In vivo Model for the Evaluation of Molecules Active Towards Transmissible Spongiform Encephalopathies - W. Ponti; M. Sala; C. Pollera; D. Braida; G. Poli; S. Bareggi (Veterinary Research Communications, 2004)

Temporal and spatial variability in settlement of the sea urchin Paracentrotus lividus in the NW Mediterranean - B. Hereu; M. Zabala; C. Linares; E. Sala (Marine Biology, 2004)

Seasonal changes in serum metabolites in free-ranging alpine marmots ( Marmota marmota ) - P. Sartorelli; S. Calderola; M. Sala; C. Citterio; P. Lanfranchi (Journal of Comparative Physiology B, 2004)

Economic Impact of Candida Colonization and Candida Infection in the Critically Ill Patient - R. Jord; J. Nolla-Salas; M. A. Len-Regidor; F. lvarez-Lerma; P. M. Olaechea; M. Palomar; C. Len-Gil (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Production of a fusion protein consisting of the enterotoxigenic Escherichia coli heat-labile toxin B subunit and a tuberculosis antigen in Arabidopsis thaliana - M. M. Rigano; M. L. Alvarez; J. Pinkhasov; Y. Jin; F. Sala; C. J. Arntzen; A. M. Walmsley (Plant Cell Reports, 2004)

Experimental Infection of Calves with Bovine Viral Diarrhoea Virus Type-2 (BVDV-2) Isolated from a Contaminated Vaccine - E. Falcone; P. Cordioli; M. Tarantino; M. Muscillo; G. Sala; G. La Rosa; I.L. Archetti; C. Marianelli; G. Lombardi; M. Tollis (Veterinary Research Communications, 2003)

A decade of collecting and research on wild potatoes of the Southwest USA - J. Bamberg; A. del Rio; Z. Huaman; S. Vega; M. Martin; A. Salas; J. Pavek; S. Kiru; C. Fernandez; D. Spooner (American Journal of Potato Research, 2003)

Silicate and labile DOC interfere in structuring the microbial food web via algal—bacterial competition for mineral nutrients: Results of a mesocosm experiment - Harry Havskum; T. Frede Thingstad; Renate Scharek; Francesc Peters; Elisa Berdalet; M. Montserrat Sala; Miquel Alcaraz; Jan C. Bangsholt; Ulla Li Zweifel; Åke Hagström; Maite Perez; John R. Dolan (Limnology and Oceanography, 2003)
The effects of organic and inorganic nutrient enrichments on algal‐bacterial competition were investigated using mesocosms. Interactions were followed over 10 d in 12, 3−m 3 seawater mesocosms in the Isefjord, Denmark. Two sets of four mesocosms were given the same daily addition of “phytoplankton nutrients” (phosphate and nitrate) but received different amounts of glucose, and one set was kept in excess with respect to silicate. Four additional mesocosms served as controls and received either no additions, silicate alone, or glucose alone. In the mesocosm set where no silicate was added, enrichment with phytoplankton nutrients and glucose led to a replacement of diatoms, not by other algae, but by heterotrophic bacteria, mainly bacteria > 2 µ. In the mesocosm set where silicate was kept replete, diatoms competed successfully with bacteria for the uptake of mineral nutrients. Even in mesocosms enriched with high amounts of glucose, primary production increased throughout the experimental period, while bacterial production, after an initial increase, leveled off. In addition, turnover time of glucose increased in the silicate‐replete mesocosm set, consistent with the idea that bacterial consumption was hampered by diatoms competing successfully for phosphate and nitrate. The size and shape of different algal and bacterial groups in relation to nutrient uptake and grazer avoidance are discussed. Both accumulation and consumption of dissolved organic carbon could depend on the structure of the microbial food web.

Prevalence and Drug Susceptibility of Pathogens Causing Bloodstream Infections in Northern Italy: A Two-Year Study in 16 Hospitals - F. Luzzaro; E. F. Viganò; D. Fossati; A. Grossi; A. Sala; C. Sturla; M. Saudelli; A. Toniolo (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Multicenter Study of a Commercial, Automated Polymerase Chain Reaction System for the Rapid Detection of Mycobacterium tuberculosis in Respiratory Specimens in Routine Clinical Practice - M. Bogard; J. Vincelette; R. Antinozzi; R. Alonso; T. Fenner; J. Schirm; D. Aubert; C. Gaudreau; E. Sala; M. Ruiz-Serrano; H. Petersen; L. Oostendorp; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2001)

Genomic changes in transgenic rice (Oryza sativa L.) plants produced by infecting calli with Agrobacterium tumefaciens - M. Labra; C. Savini; M. Bracale; N. Pelucchi; L. Colombo; M. Bardini; F. Sala (Plant Cell Reports, 2001)

The mtmVUC genes of the mithramycin gene cluster in Streptomycesargillaceus are involved in the biosynthesis of the sugar moieties - A. González; L. L. Remsing; F. Lombó; M. J. Fernández; L. Prado; A. F. Braña; E. Künzel; J. Rohr; C. Méndez; J A. Salas (Molecular Genetics and Genomics, 2001)

Erratum to:Gating of α3β4 neuronal nicotinic receptor can be controlled by the loop M2-M3 of both α3 and β4 subunits - Salvador Sala; J. C. Rovira; F. Vicente-Agulló; A. Campos-Caro; M. Criado; F. Sala; J. J. Ballesta (Pflügers Archiv - European Journal of Physiology, 2000)

Antimicrobial susceptibility testing of dematiaceous filamentous fungi: Effect of medium composition at different temperatures and times of reading - C. Llop; J. Sala; D. D. Riba; J. Guarro (Mycopathologia, 1999)

What effect can minimum restrictions produce in a coral reef area? - J.E. Arias-González; V. Castañeda; C. González-Salas; C. Cáceres; R. Garza; A. Maldonado; E. Nuñez-Lara (Coral Reefs, 1999)

Internal initiation of translation efficiency in different hepatitis C genotypes isolated from interferon treated patients - J. C. Sáiz; S. López de Quinto; N. Ibarrola; F.-X. López-Labrador; J.-M. Sánchez-Tapias; J. Rodés; E. Martínez-Salas (Archives of Virology, 1999)

Grassland Precipitation-Use Efficiency Varies Across a Resource Gradient - José M. Paruelo; William K. Lauenroth; Ingrid C. Burke; Osvaldo E. Sala (Ecosystems, 1999)

Three Cases of Tuberculosis after Heart Transplantation in Spain - R. M. Muñoz; L. A. Pulpón; M. Yebra; J. Segovia; M. San Martín; C. Salas (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Tail and eye movements evoked by electrical microstimulation of the optic tectum in goldfish - L. Herrero; F. Rodríguez; C. Salas; B. Torres (Experimental Brain Research, 1998)

During intense exercise, obese women rely more than lean women on aerobic energy - A. Ardévol; C. Adán; L. Franco; P. García-Lorda; F. Rubio; X. Remesar; J. A. Fernández-López; J. Salas-Salvadó; M. Alemany (Pflügers Archiv - European Journal of Physiology, 1998)

Intraocular candidiasis in candidemic patients - S. P. Donahue; V. L. Yu; J. Nolla-Salas; C. León-Gil (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Structure and expression inE. coli of the gene coding for protein p10 of African swine fever virus - M. Muoz; J. M. P. Freije; M. L. Salas; E. Viuela; C. Lpez-Otn (Archives of Virology, 1993)

Microbial and biochemical characterization of a bacterial consortium isolated from decaying wood by growth on a ?-O-4 lignin-related dimeric compound - Ricardo Cspedes; Loreto Salas; Ins Caldern; Bernardo Gonzles; Rafael Vicua (Archives of Microbiology, 1992)